Effects of Cholesterol and Solution pH on Daptomycin-bilayer Interactions - Samuel R. Pennock; Maggie Cortes; Megha D. Salecha; Neil X. Sevilla; Nicole R. Rementer; Kevin Rana; Luke C. Hicks; Emmaleigh Fox; Ahmed Grine; Patience S. Hammel; Timothy D. Vaden; Benjamin R. Carone; et al. (The Journal of Membrane Biology, 2026)

Forced indoors: are changing cattle husbandry practices turning a rapidly declining bird species into a pest? - Henning Heldbjerg; Malene Budde; Erik Rattenborg; Betina B. Tvistholm; Anthony D. Fox (European Journal of Wildlife Research, 2026)
Increasing farmer complaints about common starlings Sturnus vulgaris depredating maize silage on Danish dairy farms initiated an investigation of whether the growth in larger herds kept indoors year-round fed maize silage was exacerbating this conflict. Agriculture statistics showed a strong positive correlation between maize area and dairy cattle numbers in 81 Danish municipalities, confirming indoor maize silage feeding practices influences maize distribution nationally. Questionnaire returns from large (> 500 dairy cows) farms reported starlings present at 41% of farms where cattle grazed pasture, compared to 78% without grazing (where cattle are fed mainly maize silage). Starling numbers reported in cowsheds highly correlated with herd size and regional starling counts, peaking where large dairy herds were concentrated. Increasing cattle concentrations in large open cowsheds attract starlings to highly concentrated food resources in autumn when birds gather in larger flocks to migrate to winter quarters. Lost grazed grassland to maize production (to provide maize silage to cattle indoors) has denied starlings of invertebrate food formerly derived from pasture, incentivising feeding on cattle maize silage feed inside sheds, escalating conflict with farmers even as starlings continue to very rapidly decline across much of Europe. These conflicts arise from intensified year-round indoor dairy production in larger herds, reliant on nearby maize silage and reduced pasture that formerly supported invertebrate-feeding starlings. These trends have created fewer, high density “hot spots” where both cattle and starlings are concentrated. Mitigating these issues while protecting declining starling populations remains the key research and conservation challenge.

Delivering biologically safe stored water in low-resource settings using in-situ electrochemical activation - Gillian E. Clayton; Robin M.S. Thorn; Bethany G. Fox; Madhusudhan Reddy; Jean-Luc Raharison; Jean Freddy Ranaivoarisoa; Jon Shepherd; Mark D. Steer; Darren M. Reynolds (Journal of Water Process Engineering, 2026)

Corrigendum to ‘A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management’ [Earth-Science Reviews 278 (2026) 1-28] - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Assessing shortnose sturgeon response to estuarine dredging in the Savannah River using a before-after control-impact (BACI) approach - Hunter J. Rider; Katie M. Morgan; Alan T. Bond; Joseph D. Nolan; Adam G. Fox; Martin J. Hamel (Environmental Biology of Fishes, 2026)
Estuaries are productive ecosystems that support diverse aquatic species and human economies through fisheries, recreation, and navigation. However, coastal development and dredging have altered the ecological processes of estuarine habitats. In the Savannah River estuary, the Savannah Harbor Expansion Project (SHEP) deepened the river’s navigational channel by dredging to amplify vessel commerce. The endangered shortnose sturgeon ( Acipenser brevirostrum ) relies on estuarine habitat in the Savannah River to complete its life cycle; the SHEP dredging was predicted to decrease estuarine habitat availability for the local population of shortnose sturgeon. To assess population trends in relation to the SHEP, we conducted mark-recapture sampling for shortnose sturgeon in the Savannah River in the summers of 2013–2024 and used Huggins closed population capture-recapture models to estimate annual juvenile and adult abundances. We applied a before-after control-impact (BACI) model approach to compare changes in demographic-based abundances over time in the Savannah River to abundances in the geographically proximate, relatively unaltered Altamaha River. The BACI model indicated a significant decline in juvenile abundance in the Savannah River during and after the SHEP, while adult abundance remained unchanged. The timeframe of this decline and the absence of juvenile declines in the reference river suggest it may be associated with dredging via the SHEP. Juvenile declines may further threaten recovery of the Savannah River population. Continued population-level monitoring efforts and protection of the remaining estuarine habitat are critical for the long-term persistence of the Savannah River shortnose sturgeon population.

Mesolimbic and mesocortical pathways differentially support fentanyl-context associations - Annalisa Montemarano; Hajra Sohail; Laura B. Murdaugh; Kyrsten Derr; Farrah A. Alkhaleel; Logan D. Fox; Samiksha Pandey; Megan E. Fox (Psychopharmacology, 2026)
Rationale Synthetic opioids like fentanyl are contributing to unprecedented overdose rates, yet the neural circuitry underlying fentanyl-associated behaviors remains poorly understood. The ventral tegmental area (VTA) projects to both the nucleus accumbens (NAc) and prefrontal cortex (PFC), forming distinct pathways that are implicated in drug-cue associations, though their specific roles in fentanyl-context encoding are not well defined. Objectives This study aimed to determine how VTA-NAc and VTA-PFC circuits contribute to fentanyl-context associations, and to assess the role of downstream dopamine receptor signaling in fentanyl context-seeking. Methods Male and female mice underwent fentanyl conditioned place preference (CPP; 0.2 mg/kg). We locally inhibited dopamine D1 or D2 receptors in NAc or PFC during CPP expression. We used fiber photometry calcium imaging to measure activity in VTA-NAc and VTA-PFC projection neurons, and chemogenetic inhibition to suppress activity during CPP expression. Results Fentanyl CPP expression was attenuated by blocking D1 but not D2 receptors in PFC, and D2 but not D1 receptors in NAc. We found both VTA-NAc and VTA-PFC exhibited increased calcium activity during fentanyl exposure and during entries to the fentanyl-paired context. We further identified a functional role for VTA-NAc, as chemogenetic inhibition of VTA-NAc, but not VTA-PFC, reduced fentanyl context-seeking. Conclusions While both VTA-NAc and VTA-PFC pathways are recruited by fentanyl exposure, fentanyl context-seeking relies on different downstream dopamine receptors in NAc vs PFC. Further, activity in VTA-NAc functionally supports the expression of fentanyl CPP. Together, these findings indicate that VTA circuits differentially contribute to fentanyl context-seeking.

Wicked problems in practice: Responding to ecological transformation in wilderness - Jaclyn Fox Rushing; Kira Hefty; Teresa N. Hollingsworth; Amanda E. Cravens; Christopher A. Armatas; Clare Boerigter; Kellie J. Carim; Shelley D. Crausbay; Olga Helmy; David J. Lawrence; Lauren Redmore; Gregor W. Schuurman; et al. (Ambio, 2026)
Congressionally designated wilderness offers the highest level of land protection in the USA, comparable to category 1b wilderness as defined by the International Union for Conservation of Nature, yet wilderness areas face impacts of climate change. Researchers and managers increasingly recognize the immense challenge of stewarding wilderness in a changing climate. Although responding to climate change is considered a wicked problem, this framing has not been applied to wilderness contexts. We move theory into practice by using wicked problem framing and four illustrative cases to explore how the resist–accept–direct (RAD) framework can help untangle the wicked problem of addressing unprecedented ecological transformation in wilderness. The RAD framework clarifies a range of response options including resisting transformation, accepting it, or directing it toward preferred new conditions. As climate change continues to challenge wilderness managers, the RAD framework can help assess trade-offs and preserve wilderness character into the twenty-first century.

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

First report of narcissus late season yellows virus (NLSYV) in Sternbergia lutea in the United Kingdom - Andrew Leng; Mary Mynett; Stephen M. D. Forde; Aimee R. Fowkes; Sarah Eustace; Leanne Frew; Richard Ward; Anna Skelton; Adrian Fox (Journal of Plant Pathology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Continental‐wide prioritization of protected areas to address global and habitat‐specific goals for avian biodiversity conservation - Yanjie Xu; Diego Pavón‐Jordán; Tyler Hallman; Tristan R. M. Bakx; Lluís Brotons; Sergi Herrando; Alison Johnston; Brett K. Sandercock; Thomas Sattler; Alaaeldin Soultan; Vitalie Ajder; Dawn E. Balmer; et al. (Conservation Biology, 2026)
The United Nations and European Union have set ambitious conservation goals to halt and reverse declines in biodiversity by protecting 30% of land and sea areas by 2030. Effective conservation planning requires evidence‐based spatial prioritization to maximize the coverage of species within designated protected areas. Based on a pan‐European database for occurrence and abundance of breeding birds collected in the 2010s, we applied the Zonation algorithm to identify key areas that would maximize the protection of ranges and populations for 435 species of breeding birds across Europe using either continental or national prioritization targets. When 30% of Europe's highest priority terrestrial areas were selected by the algorithm, 49% of species’ ranges and 63% of species’ populations were protected. When 10% and 30% of the highest priority lands were selected, compared with prioritization using occurrence data, prioritization using abundance data resulted in a higher percentage of species’ populations, especially rare and range‐restricted species, being represented for protected area coverage. Stratifying prioritization by habitat criteria greatly enhanced habitat‐specific conservation efficiency, enabling coverage of over 80% of breeding bird species’ populations in tundra, Mediterranean, and coastal habitats with a selection of 10% of the highest priority areas for each. Our prioritization supports international targets adopted under the Kunming–Montreal Global Biodiversity Framework by identifying key areas and providing a roadmap to guide optimal site protection and conservation planning in Europe.

The Scotland–Canada overturning array (SCOTIA): twenty years of meridional overturning in the subpolar North Atlantic - Alan D. Fox; Neil J. Fraser; Kristin Burmeister; Sam C. Jones; Stuart A. Cunningham; Lewis A. Drysdale; Ahmad Fehmi Dilmahamod; Johannes Karstensen (Ocean Science, 2026)
The Atlantic meridional overturning circulation (AMOC) is expected to decline dramatically over the 21st century, with severe impacts for Northern Hemisphere climate. After 20 years of sustained monitoring in the subtropics, a detectable AMOC weakening trend is now beginning to emerge. However, continuous observations at subpolar latitudes are currently too short-lived to determine any weakening signal above the large-amplitude interannual variability. Here, we introduce a new subpolar observing configuration, SCOTIA (Scotland–Canada overturning array), combining parts of the existing OSNAP mooring array with scattered CTD and Argo data, to extend the record of subpolar AMOC backward in time to cover the subtropical monitoring period, 2004–2024. SCOTIA facilitates a rigorous comparison of the decadal-scale variability in transports and overturning at subpolar and subtropical latitudes. Our results show subpolar AMOC varies on pentadal to decadal timescales with an amplitude comparable to that observed in the subtropics. Anomalously high overturning during 2016–2020 was driven by increased southward transports in the density classes associated with Labrador Sea Water. We find no statistically significant trend in subpolar AMOC during the period 2004–2024.

Expanding insights into plant rhabdovirus diversity through the discovery of viruses representing 32 putative novel species - Marleen Botermans; P. P. M. de Koning; M. Westenberg; I. P. Adams; K. Ben Mansour; C. Chabi-Jesus; C. de Krom; A. M. Dullemans; R. Festus; A. R. Fowkes; A. Fox; J. Freitas-Astúa; et al. (Archives of Virology, 2026)
Plant-infecting rhabdoviruses (family Rhabdoviridae , subfamily Betarhabdovirinae ) include several viruses that cause important crop diseases and are subject to phytosanitary regulation. Despite their agricultural and ecological importance, the diversity of plant rhabdoviruses and their impact on plant health remain poorly understood. Here, we report 32 tentative novel species of plant-infecting rhabdoviruses, identified via high-throughput sequencing and spanning nine established genera. The virus sequences originated from diverse hosts and geographic regions, revealing extensive diversity within the family Rhabdoviridae . Several viruses were detected independently in the same host species across multiple countries, demonstrating the practical value of data sharing for confirming host associations and gaining insight into the geographic distribution of these viruses. Our study highlights the underexplored diversity of plant rhabdoviruses and demonstrates the value of coordinated, collaborative virus discovery. With HTS now widely accessible, the challenge has shifted from virus discovery to making sequence data and metadata publicly available, and to conducting the time-consuming biological characterization often deprioritized in favour of viruses with immediate phytosanitary relevance. As a result, many findings remain unreported, leaving valuable data dormant on servers. By sharing genomic data prior to publication, we present an efficient approach to accelerate virus reporting, enable comparative analyses and advance understanding of virus diversity. We hope this collaborative effort will encourage further exploration of plant viruses, including those from hosts without discernable symptoms, supporting virus biology, taxonomy, pest risk assessments, and plant health policies.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Exposure risk of alcids to marine vessel-associated oil pollution in Western Canada - Patrick D. O'Hara; Sonya Pastran; Douglas F. Bertram; Alexandra King; Mathieu Bourbonnais; Paul Barrett; Laurie Wilson; Ken H. Morgan; Caroline H. Fox; Gary W. Kaiser; Vivian Pattison; Leh Smallshaw; et al. (Science of The Total Environment, 2026)

Hydrologic variability drives environmental and geospatial relationships in Smallmouth Bass (Micropterus dolomieu) distribution - Sarah F. Sorensen; J. Tyler Fox; Daniel D. Magoulick (Science of The Total Environment, 2026)

Diet composition of a generalist predator does not indicate its population impact on prey: a response to Pagh et al. (2025) - Peter Sunde; Sari Holopainen; Morten Elmeros; Heidi Krüger; Malin Aronsson; Fredrik Dahl; Kim Jaatinen; Per-Arne Åhlén; Anthony D. Fox (European Journal of Wildlife Research, 2026)

Assessing direct effects of insect change on insectivore populations in the United Kingdom - L. C. Evans; M. D. Burgess; S. G. Potts; W. E. Kunin; R. Fox; K. E. Powell; K. Boughey; C. A. Harrower; Y. Bourhis; B. Martay; T. H. Oliver (Biodiversity and Conservation, 2026)
Declines in insect abundance are a cause for concern, with potential downstream impacts on ecosystem function. Insects are key food resources for insectivorous vertebrates, with evidence that reductions in prey availability may influence population dynamics. Yet quantifying direct effects at large spatial scales is difficult, both due to data limitations and because correlations may reflect shared responses to environmental change rather than trophic links. We assess the role of insect abundance in the dynamics of 10 insectivores (five birds, five bats) in the United Kingdom by pairing insect and vertebrate abundance data at three spatial resolutions (100, 50, 10 km) from multiple citizen science programmes. To address the challenges of inference and combining heterogeneous data, we adopt a multiple-specification approach spanning: (1) association, (2) prediction, and (3) causal inference. We found evidence of overall declines for all bird species evaluated and for most indices of insect abundance, though none of the bat species tested showed consistent declines. Despite indices of both insect and bird abundance declining, declines did not always co-occur spatially. We also detected only moderate evidence of links between insect change and insectivore population change, notably blue tit and great tit with moth abundance, and grey partridge with Diptera abundance. Across taxa, spatial scales, and analytical approaches, we did not find consistent evidence that changes in insect abundance are a dominant driver of insectivore declines. Both insects and insectivores may instead be responding to multiple, and sometimes non-overlapping, pressures associated with environmental change. We emphasise that absence of strong evidence does not imply absence of effect, and highlight the difficulties of drawing direct conclusions from heterogeneous observational monitoring data.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Initiation of dolutegravir vs. efavirenz on 12- and 24-month retention and viral suppression: a target trial emulation - Amy Zheng; Alana T. Brennan; Ross Greener; Emma M. Kileel; Jacob Bor; Willem D. F. Venter; Eleanor J. Murray; Pedro T. Pisa; Bridgette Goeieman; Matthew P. Fox; Mhairi Maskew (Infectious Diseases, 2026)

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

Discovery of new Australasian Rare Earth Element hyperaccumulator ferns from screening herbarium specimens - Amelia Corzo-Remigio; Imam Purwadi; Nathan Fox; Peter D. Bostock; Carlos Martel; Antony van der Ent; Peter D. Erskine (Plant and Soil, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Stable Isotope Ecology of the Early Miocene Rusinga Island Mammalian Communities from the Hiwegi and Kulu Formations (Nyanza Province, Western Kenya) - David L. Fox; Nicole D. Garrett; Daniel J. Peppe; Lauren A. Michel; Kirsten Jenkins; Thomas Lehmann; Kieran P. McNulty (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Longest documented coastal migrations of shortnose sturgeon - Joseph D. Nolan; William C. Post; Ellen Waldrop; Joseph J. Facendola; Michael S. Loeffler; William Collier; Evan C. Ingram; Martin J. Hamel; Adam G. Fox (Journal of Fish Biology, 2025)
The shortnose sturgeon (SNS; Acipenser brevirostrum ) is a United States federally endangered diadromous species. Although SNS spend much of their time in riverine habitat, inter‐river migrations have been documented in northern populations. However, the inter‐river migratory behaviour and distance capabilities of southern SNS are poorly understood. In this communication, we describe two SNS that migrated approximately 425 km across the coast, far exceeding the previously reported maximum coastal migration distance for the species. These observations offer critical updates for species descriptions and management regarding the coastal migration ability of SNS.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Climate change impacts to upwelling and shallow reef nutrient sources across an oceanic archipelago - Danielle L. Spring; Michael D. Fox; J. A. Mattias Green; Robin Guillaume‐Castel; Zoe Jacobs; Ronan C. Roche; John R. Turner; Gareth J. Williams (Limnology and Oceanography, 2025)
Upwelling delivers key nutritional and energetic subsidies to coral reef communities that affect the growth, abundance, and ecology of organisms across trophic levels. However, the cross‐scale oceanographic and atmospheric drivers of localized upwelling on many reefs remain unresolved, limiting our ability to predict how climate change might disrupt upwelling patterns and impact reef communities across geographies. Using high temporal resolution (10 second) in situ temperature measurements collected over 18 months that encompassed the strongest positive Indian Ocean Dipole phase of this century, we demonstrate a highly nonlinear effect of climate‐driven mixed layer depth on upwelling intensity across the latitudinal range of the Chagos Archipelago (~ 200 km). The exposure of shallow (10–25 m depth) reef communities to deeper upwelled waters was maximized when the mixed layer depth was shallower than ~ 40 m, but virtually absent when the mixed layer depth was deeper than ~ 60 m. By combining these temperature data with nitrogen stable isotopes (δ 15 N) from a common macroalga, we show these variations in upwelling correlate with altered nutrient sources that have direct measurable impacts on reef organisms across the Archipelago. We further show that over the past 40 years, positive phases of the Indian Ocean Dipole correlate with an anomalously deep surface mixed layer on these reefs, each time likely restricting upwelling. Given these extreme events are increasing in frequency under climate change, this poses the possibility of a markedly different upwelling regime across the Archipelago over the coming century, with currently unknown ecological consequences.

From Data Deficient to Big Data in Shark Conservation - F. Ferretti; J. Jenrette; S. Moro; C. Butner; E. Fox; S. H. D. Haddock; S. J. Jorgensen; T. Hastie; F. Micheli (Fish and Fisheries, 2025)
Citizen science is increasingly harnessed worldwide to gather data otherwise requiring a prohibitive investment of funding and time. Meanwhile, the revolution in digital communication offers opportunities from crowdsourcing, big data approaches and social network mining to quickly and cost‐effectively fill major gaps in knowledge necessary to protect endangered populations. Sharks are among the most endangered and data‐poor vertebrates in the ocean. Mainly due to overfishing, many shark populations are declining worldwide, while most species lack basic abundance, distribution and life‐history data. Hence, filling knowledge gaps across taxa, ecosystems, and regions is urgently needed to increase our understanding of their ecology, develop effective conservation actions and reverse their loss. Here, we introduce a novel citizen science and crowdsourcing approach for conservation through sharkPulse, a new platform automating data ingestion and organisation to build the largest database of shark occurrence records to date. Designed to complement and extend similar biodiversity monitoring tools relying heavily on user submissions, sharkPulse aims to source large streams of online shark images and transform them into occurrence records, filling knowledge gaps in shark ecology and biology. This platform offers a blueprint to leverage AI and big data approaches, social network data mining and participatory science to efficiently and continuously source visual media materials and transform the monitoring of data‐limited marine and terrestrial animal populations.

A modeling framework to meta-analyse discard survival experiments illustrated by Nephrops norvegicus in European demersal trawl fisheries - M. Morfin; E. Savina; H.P. Benoît; M. Teixeira Alves; A. Albalat; T. Catchpole; C. Fox; M. McHugh; S. Méhault; H. Nilsson; M. Oliver; D. Valentinsson; et al. (Fisheries Research, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Accreted volatiles influence low-temperature rock equilibria on Europa - Nisha K. Ramkissoon; Mark G. Fox-Powell; Lewis Sym; Martin D. Suttle; Alvaro Del Moral; Victoria K. Pearson (Icarus, 2025)

Seasonality of meridional overturning in the subpolar North Atlantic: density flux as a metric for understanding the Atlantic meridional overturning circulation - Alan D. Fox; Neil J. Fraser; Stuart A. Cunningham (Ocean Science, 2025)
The Atlantic meridional overturning circulation (AMOC) has a notable seasonal component. This influences the jet stream and the location, frequency, and intensity of extreme weather events. Understanding this seasonality is important for mitigating the impacts of AMOC changes on European weather and climate. Here, we place meridional overturning and fluxes in a coherent framework. This framework highlights the integral relationship between meridional overturning circulation and property transports, both being functions purely of the overturning streamfunction Ψ. Using this framework, we examine the seasonality observed in overturning and density, temperature, and freshwater fluxes at the Overturning in the Subpolar North Atlantic Program (OSNAP) line in the subpolar North Atlantic. We find the seasonal cycle of the MOC metric (the standard measure of overturning, defined as the maximum of the overturning streamfunction) to be dominated by Ekman transports and the large-scale seasonal cycle of surface density; heat flux to be dominated by barotropic velocity variability; the seasonal cycle of freshwater flux to be dominated by a combination of barotropic velocities and the salinity in the western boundary current; and density flux to reflect a broad range of characteristics and processes. We show that the MOC metric is a poor predictor, on seasonal timescales, of either density fluxes or the more societally relevant ocean heat and freshwater transports. This is due to each of these metrics responding to different physical processes. The MOC metric, on seasonal timescales at least, has very high sensitivity to near-surface physical characteristics in a limited geographical area. These characteristics are not necessarily reflective of the fundamental processes driving overturning. Therefore, we suggest caution in the use of the standard MOC metric when studying overturning and the routine use of the density flux as a valuable additional overturning metric.

Bioconcentration and toxicity of perfluoroalkyl substances (PFAS) in embryonic stages of the ecologically and commercially relevant Olive Flounder (Paralichthys olivaceus), and the zebrafish (Danio rerio) embryo model system - Kiflom Gebreab; Ariel Lawson; Giancarlos Garcia; Jessica Fox; Daniel Benetti; John D. Stieglitz; Natalia Soares Quinete; John P. Berry (Ecotoxicology, 2025)

Developmental Behavioural Plasticity and DNA Methylation Patterns in Response to Predation Stress in Trinidadian Guppies - Janay A. Fox; Simon M. Reader; Mélanie F. Guigueno; Rowan D. H. Barrett (Molecular Ecology, 2025)
Early‐life experiences can predict the environments experienced later in life, giving individuals an opportunity to develop adaptive behaviour appropriate to a likely future environment. Epigenetic mechanisms such as DNA methylation (DNAm) have been implicated in developmental behavioural plasticity; however, studies investigating this possibility are limited in taxonomic breadth and ecological relevance. We investigated the impact of early‐life exposure to predation stress on behaviour and DNAm in the brains of Trinidadian guppies ( Poecilia reticulata ). We exposed guppies throughout development to either an alarm cue (conspecific skin extract), inducing predation stress, or a control cue (water) for 8 weeks and then raised them to adulthood under identical conditions. Then, we conducted two behavioural assays, an open‐field and a grouping test, before performing whole‐genome bisulfite sequencing on whole brains. Guppies exposed to the alarm cue during development exhibited increased grouping (shoaling) in adulthood compared to those exposed to the control treatment, but there were no detectable impacts on activity, boldness, or exploratory behaviour. We also identified stable shifts in brain DNAm in response to developmental alarm cue exposure in genes involved in behavioural regulation. Some differentially methylated sites were significantly associated with shoaling propensity in both males and females. Additionally, males and females differed in the magnitude of DNAm responses and the genes impacted, suggesting distinct roles for DNAm between the sexes. This study shows how early‐life predation stress can induce behavioural changes in adulthood and that shifts in neural DNAm could be an underlying mechanism responsible for these changes.

Heterotrophy of particulate organic matter subsidies contributes to divergent bleaching responses in tropical Scleractinian corals - Connor R. Love; Kelly E. Speare; Michael D. Fox; Veronica Z. Radice; Kelton W. McMahon; Gretchen E. Hofmann; David L. Valentine; Marie E. Strader (Limnology and Oceanography, 2025)
Heterotrophic feeding on plankton and particulate organic matter (POM) by tropical Scleractinian corals is known to aid in the resistance and recovery from thermally induced bleaching. However, the relative importance of heterotrophy in promoting bleaching resistance and recovery is likely to vary based on ecological context and the severity of heat stress. In 2019, the Pacific Island of Mo'orea experienced mass coral mortality during a widespread marine heatwave. Many Acropora hyacinthus colonies on the shallow reef slope (5 m) were resistant to bleaching, while colonies on the deeper fore reef (14 m) often bleached and subsequently recovered, despite similar thermal stress. The role of heterotrophy in this divergent bleaching response was investigated using fatty acid (FA), isotopic, and elemental biomarkers. Multiple complementary lines of evidence, including feeding proxies, isotopic niche overlap, and putative POM FA biomarkers, indicated that bleaching resistant colonies were likely consuming more POM than their bleached and recovered counterparts. Additionally, although visually recovered, host energetics in recovered colonies remained compromised and exhibited proportionally less monounsaturated and polyunsaturated FAs and less relative nitrogen than resistant colonies. We show that corals that rely more on heterotrophic nutrient acquisition can better resist thermally induced bleaching. Our results also revealed the long‐term energetic costs of bleaching even after visual recovery. Ultimately, these results underscore the vital role of coral nutrition in shaping coral bleaching response and recovery.

Impact of severe tropical cyclone Winston on fisheries-dependent communities in Fiji - Alyssa S. Thomas; Sangeeta Mangubhai; Katherine Chaston Radway; Margaret Fox; Stacy D. Jupiter; Watisoni Lalavanua; Marita Manley; Alisi Rabukawaqa (Environmental Development, 2025)

Temporary Absence of Warming in the Northern Weddell Sea Validates Expected Responses of Antarctic Seals to Sea Ice Change - M. J. Dunn; C. M. Waluda; S. Adlard; D. Fox; A. S. Lynnes; T. I. Morley; J. Forcada (Global Change Biology, 2025)
The temporal abundance of Antarctic seals is known to be influenced by variation in the sea ice environment, itself affected by temperature and daylight cycles across seasons. However, the sensitivity of seal populations to changes in their environment beyond expected natural variation depends on their abilities to deal with extreme conditions and to take advantage of favourable environmental changes, which is rarely validated empirically. Here, we report on the responses of three sympatric Antarctic seal species to sea ice change: two ‘ice‐tolerant’ species: Antarctic fur seal Arctocephalus gazella and southern elephant seal Mirounga leonina , and the ‘ice‐obligate’ Weddell seal Leptonychotes wedellii , over a 48‐year period from 1977 to 2024 at Signy Island, South Orkney Islands. This area has undergone changes in the sea ice environment following persistent long‐term warming since the 1950s, and a cooling period from approximately 1998–2014. The shared environment and varying adaptation to sea ice of the three species presented a unique opportunity to assess and compare species‐specific responses to fluctuating sea ice cycles, and validate predictions of responses from projections of sea ice change. Across five decades, all three species were significantly affected by temporary changes in the sea‐ice environment, which contributed to synchronous between‐year variation in numbers, although density dependence was an important effect for each species. Maximum synchrony between seal species was observed from the late 1990s to mid‐2000s, coinciding with the temporary absence of warming, with the ice obligate Weddell seal benefiting from an extended sea ice season but not the two ice‐tolerant species. Numbers of Antarctic fur seals and Weddell seals declined significantly between 1977 and 2024 by approximately 47% and 54% respectively, from a peak in 1994 and 1985, although no significant overall long‐term decline in the numbers of southern elephant seals was found, despite trend synchronicity.

Rapid Neural DNA Methylation Responses to Predation Stress in Trinidadian Guppies - Janay A. Fox; Simon M. Reader; Rowan D. H. Barrett (Molecular Ecology, 2025)
DNA methylation (DNAm) is a well‐studied epigenetic mechanism implicated in environmentally induced phenotypes and phenotypic plasticity. However, few studies investigate the timescale of DNAm shifts. Thus, it is uncertain whether DNAm can change on timescales relevant for rapid phenotypic shifts, such as during the expression of short‐term behavioural plasticity. DNAm could be especially reactive in the brain, potentially increasing its relevance for behavioural plasticity. Most research investigating neural changes in methylation has been conducted in mammalian systems, on isolated individuals, and using stressors that are less ecologically relevant, reducing their generalisability to other natural systems. We exposed pairs of male and female Trinidadian guppies ( Poecilia reticulata ) to alarm cue, conspecific skin extract that reliably induces anti‐predator behaviour, or a control cue. Whole‐genome bisulphite sequencing on whole brains at various time points following cue exposure (0.5, 1, 4, 24, and 72 h) allowed us to uncover the timescale of neural DNAm responses. Males and females both showed rapid shifts in DNAm in as little as 0.5 h. However, males and females differed in the time course of their responses: both sexes showed a peak in the number of loci showing significant responses at 4 h, but males showed an additional peak at 72 h. We suggest that this finding could be due to the differing longer‐term plastic responses between the sexes. This study shows that DNAm can be rapidly induced by an ecologically relevant stressor in fish and suggests that DNAm could be involved in short‐term behavioural plasticity.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Coral reef thermal microclimates mapped from the International Space Station - J. Longenecker; F. Benzoni; N. Dunn; H. E. Fox; A. Gleason; D. Otis; V. Chirayath; N. Oury; S. J. Purkis (Coral Reefs, 2025)
Satellite sea surface temperature (SST) is critical for describing marine environments. Traditional SST data, such as those provided by the Group for High Resolution Sea Surface Temperature (GHRSST) program, are valuable, but have a relatively coarse spatial resolution for mapping coral reef thermal environments. Hence, fine resolution SST from orbit would be of great utility to the coral reef research community and speed the pathway to an increased understanding of how, when, and where thermal stress afflicts individual reefs. Such data would support adaptive management, especially so for the design of marine protected areas. Flying aboard the International Space Station, the NASA ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) instrument may already fill this niche with a spatial resolution 204 times finer than GHRSST. To evaluate ECOSTRESS thermal data over reef environments, we deployed 21 temperature loggers over three years across two reef sites in the Red Sea. We compared temperature retrievals from both the coarse resolution GHRSST and the fine resolution, experimental, ECOSTRESS, to this in-situ logger dataset. While temperature data from both orbital platforms correlated strongly with the logger recordings, only ECOSTRESS, with its 70-m pixels, could construct thermal microclimate maps capturing the dynamic temperature fluctuations experienced by our studied reefs. We contend that ECOSTRESS represents a significant advancement in the capability to monitor heat stress on reefs from orbit.

Six decades of global coral bleaching monitoring: a review of methods and call for enhanced standardization and coordination - Andrea Rivera-Sosa; Aarón Israel Muñiz-Castillo; Ben Charo; Gregory P. Asner; Chris M. Roelfsema; Simon D. Donner; Brianna D. Bambic; Ana Gabriela Bonelli; Morgan Pomeroy; Derek Manzello; Paulina Martin; Helen E. Fox (Frontiers in Marine Science, 2025)
Coral bleaching poses a severe threat to the health and survival of global coral reef ecosystems, with recent events surpassing historical heat stress records. To address this crisis, improved long-term monitoring, communication, and coordination are urgently required to enhance conservation, management, and policy responses. This study reviews global coral bleaching survey methodologies and datasets spanning 1963 to 2022, identifying key challenges in methodological standardization, including database duplication and inconsistencies in naming and reporting bleaching metrics. These issues hinder comparative analyses and contribute to discrepancies in global bleaching impact assessments. We developed a typology of twenty-nine coral bleaching methods used across various scales, encompassing remote sensing tools, underwater surveys, and specimen collection. Analysis of 77,370 observations from three major datasets revealed that 9.36% of entries lacked methodological descriptions. Among recorded methods, belt transects (42%), line and point intercept transects (33%), and random surveys (17%) were the most widely applied. Practitioner surveys underscored the dominance of in situ transect and visual methods, highlighting the growing adoption of photo quadrats—an emerging yet underrepresented technique in existing datasets. To enhance global coral bleaching assessments, we propose a standardized framework that ensures open access and accessible data that aligns with decision-makers’ needs for efficient data aggregation and interoperability to better understand temporal and spatial bleaching events. A globally coordinated coalition should unify protocols, improve data-sharing capabilities, and empower regional networks through targeted training, incentives, and open communication channels. Strengthening field capacity in coral taxonomy and standardized survey methodologies, alongside integrating advanced tools, will improve data quality and comparability. Additionally, creating precise geolocated datasets will bridge on-the-ground observations with advanced remote sensing systems, refining the accuracy of satellite-based early warning tools. Establishing interoperable online platforms will further streamline data integration and accessibility, providing a robust foundation to support global responses to coral bleaching and foster impactful conservation initiatives.

Correction to: Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Transforming Traditional Industry Advisory Boards Into Mutually Beneficial Strategic Think Tanks: A Peer Review Council Case Series and Best Practices - Todd Williamson; John Fox; Scott Ramsey; Maria Martins-Lopes; Kevin M. Pantalone; C. Daniel Mullins; Kenneth Schaecher; Sean D. Sullivan (Journal of Pharmaceutical Innovation, 2025)

How well do connectivity tools agree over the full life cycle? A case study of Irish Sea plaice Pleuronectes platessa Linnaeus , 1758 - Audrey J. Geffen; Richard D. M. Nash; Clive J. Fox (Journal of Fish Biology, 2025)
Adult plaice in the Irish Sea have distinct traits that reflect the spawning locations that could suggest a number of different populations. However, do connectivity pathways support this concept? Different tools are directed at measuring exchange or connectivity between different life‐history stages, and the challenge is to integrate the signals to obtain full life‐cycle estimates. Collectively, the different methods reveal stable connectivity between known spawning and nursery grounds, with sufficient exchange to maintain a single population with weak genetic structure.

Benthic algal community dynamics on Palmyra Atoll throughout a decade with two thermal anomalies - Adi Khen; Maggie D. Johnson; Michael D. Fox; Jennifer E. Smith (Frontiers in Marine Science, 2025)
Coral reef algae serve many important ecological functions, from primary production to nutrient uptake and reef stabilization, but our knowledge of longer-term effects of thermal stress on algae in situ is limited. While ocean warming can facilitate proliferation of algae and potential phase shifts from coral to macroalgal-dominated states, algal responses may vary by species, genus, functional group, or type (e.g., calcareous vs. fleshy). We used 11 years of annual monitoring data (2009-2019) that spans two El Niño-associated heatwaves to examine benthic algal community dynamics on Palmyra Atoll in the central Pacific Ocean. We quantified the percent cover of algal taxa via image analysis of permanent benthic photoquadrats from two habitats on Palmyra: the deeper, wave-exposed fore reef (10 m depth) and the shallower, wave-sheltered reef terrace (5 m depth). Each habitat was characterized by distinct algal communities: predominantly calcareous taxa on the fore reef and predominantly fleshy taxa on the reef terrace. Patterns in abundance fluctuated over time and/or in response to thermal anomalies in 2009 and 2015. Fleshy algae generally increased in cover post-warming, which coincided with large declines of the calcified macroalgae, Halimeda spp. Long-term monitoring of coral reef algal communities is critical for understanding their differential responses to thermal stress and can improve projections of ecosystem functioning in the context of global change.

Breeding waterbird species as ecological indicators of shifts from turbid to clear water conditions in northwest European shallow eutrophic lakes - Anthony D. Fox; Hans E. Jørgensen; Erik Jeppesen; Torben L. Lauridsen; Martin Søndergaard; Karsten Fugl; Palle P. Myssen; Thorsten J. S. Balsby; Preben Clausen; Petr Musil; Zuzana Musilová (Hydrobiologia, 2025)
We used biological and physical responses at 71 shallow waterbodies with contrasting nutrient levels undergoing recovery from eutrophication to predict potential changes in waterbird species abundance, an important component of lake ecosystems. These general predictions were tested using 28 years of breeding waterbird data from three Danish shallow eutrophic lakes, comparing species-specific responses to improved nutrient and water transparency in two lakes with a third where conditions remained constantly suitable for breeding waterbirds. We predicted positive responses to improved water quality from pursuit diving predators (three grebe species), a specialist zooplankton feeder (northern shoveler Anas clypeata ) and waterbirds feeding on (common pochard Aythya ferina ) or within (tufted duck A. fuligula ) submerged macrophyte underwater canopies. These species were characterised by positive waterbird community composition changes (using Principal Components Analysis) associated with decreasing nutrient loading and increasing water transparency at two lakes, with no change in breeding waterbird community at the third. Secchi depth explained 73–95% of variance in both PC axes at both restored lakes, but not at the third, suggesting water transparency was the major factor driving waterbird community composition. These examples show predicting waterbird species-specific responses to management can usefully direct the use of breeding waterbirds as indicator species.

A radar backscatter simulation of a forest canopy using 3D physical structures derived from LiDAR scanning - Veronica Escobar-Ruiz; William Maslanka; Chris D. Westbrook; Keith Morrison; Kim Calders; Niall Origo; Mathias Disney; Nigel Fox (International Journal of Remote Sensing, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Role of walkability, bike infrastructure, and greenspace in combatting chronic diseases: A heterogeneous ecological analysis in the United States - Behram Wali; Lawrence D. Frank; Jim Chapman; Eric H. Fox (Sustainable Cities and Society, 2024)

Fish beta diversity associated with hydrologic and anthropogenic disturbance gradients in contrasting stream flow regimes - J. Tyler Fox; Daniel D. Magoulick (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Counter‐gradient variation in gene expression between fish populations facilitates colonization of low‐dissolved oxygen environments - Janay A. Fox; David A. G. A. Hunt; Andrew P. Hendry; Lauren J. Chapman; Rowan D. H. Barrett (Molecular Ecology, 2024)
The role of phenotypic plasticity during colonization remains unclear due to the shifting importance of plasticity across timescales. In the early stages of colonization, plasticity can facilitate persistence in a novel environment; but over evolutionary time, processes such as genetic assimilation may reduce variation in plastic traits such that species with a longer evolutionary history in an environment can show lower levels of plasticity than recent invaders. Therefore, comparing species in the early stages of colonization to long‐established species provides a powerful approach for uncovering the role of phenotypic plasticity during different stages of colonization. We compared gene expression between low‐dissolved oxygen (DO) and high‐DO populations of two cyprinid fish: Enteromius apleurogramma , a species that has undergone a recent range expansion, and E. neumayeri , a long‐established native species in the same region. We sampled tissue either immediately after capture from the field or after a 2‐week acclimation under high‐DO conditions, allowing us to test for both evolved and plastic differences in low‐DO vs high‐DO populations of each species. We found that most genes showing candidate‐evolved differences in gene expression did not overlap with those showing plastic differences in gene expression. However, in the genes that did overlap, there was counter‐gradient variation such that plastic and evolved gene expression responses were in opposite directions in both species. Additionally, E. apleurogramma had higher levels of plasticity and evolved divergence in gene expression between field populations. We suggest that the higher level of plasticity and counter‐gradient variation may have allowed rapid genetic adaptation in E. apleurogramma and facilitated colonization. This study shows how counter‐gradient variation may impact the colonization of divergent oxygen environments.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Cohesion and shear strength of compacted lunar and Martian regolith simulants - B. Dotson; D. Sanchez Valencia; C. Millwater; P. Easter; J. Long-Fox; D. Britt; P. Metzger (Icarus, 2024)

Diversification of refugia types needed to secure the future of coral reefs subject to climate change - Tim R. McClanahan; Emily S. Darling; Maria Beger; Helen E. Fox; Hedley S. Grantham; Stacy D. Jupiter; Cheryl A. Logan; Elizabeth Mcleod; Lisa C. McManus; Remy M. Oddenyo; Gautam S. Surya; Amelia. S. Wenger; et al. (Conservation Biology, 2024)
Identifying locations of refugia from the thermal stresses of climate change for coral reefs and better managing them is one of the key recommendations for climate change adaptation. We review and summarize approximately 30 years of applied research focused on identifying climate refugia to prioritize the conservation actions for coral reefs under rapid climate change. We found that currently proposed climate refugia and the locations predicted to avoid future coral losses are highly reliant on excess heat metrics, such as degree heating weeks. However, many existing alternative environmental, ecological, and life‐history variables could be used to identify other types of refugia that lead to the desired diversified portfolio for coral reef conservation. To improve conservation priorities for coral reefs, there is a need to evaluate and validate the predictions of climate refugia with long‐term field data on coral abundance, diversity, and functioning. There is also the need to identify and safeguard locations displaying resistance toprolonged exposure to heat waves and the ability to recover quickly after thermal exposure. We recommend using more metrics to identify a portfolio of potential refugia sites for coral reefs that can avoid, resist, and recover from exposure to high ocean temperatures and the consequences of climate change, thereby shifting past efforts focused on avoidance to a diversified risk‐spreading portfolio that can be used to improve strategic coral reef conservation in a rapidly warming climate.

First report of nerine yellow stripe virus in Clivia miniata in the United Kingdom - A. L. Sheppard; A. Skelton; V. Harju; R. Ward; S. M. D. Forde; A. Fox; A. R. Fowkes (Journal of Plant Pathology, 2024)

Solid tumor treatment via augmentation of bioactive C6 ceramide levels with thermally ablative focused ultrasound - E. Andrew Thim; Todd Fox; Tye Deering; Luke R. Vass; Natasha D. Sheybani; Mark Kester; Richard J. Price (Drug Delivery and Translational Research, 2023)

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

Food on a plate: Wild geese maintain higher food intake rates on uniform winter cereals fields versus diverse grasslands - Michał Polakowski; Monika Broniszewska; Łukasz Jankowiak; Anthony D. Fox (Science of The Total Environment, 2023)

Immune cell composition varies by age, sex and exposure to social adversity in free-ranging Rhesus Macaques - Mitchell R. Sanchez Rosado; Nicole Marzan-Rivera; Marina M. Watowich; Andrea D. Negron-Del Valle; Petraleigh Pantoja; Melissa A. Pavez-Fox; Erin R. Siracusa; Eve B. Cooper; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Melween I. Martinez; et al. (GeroScience, 2023)

The lure of the big city: smaller Danish rookeries are increasingly associated with urban land cover - Henning Heldbjerg; Claus Lunde Pedersen; Ole R. Therkildsen; Thomas Bregnballe; Henning Ettrup; Johnny Kahlert; Thomas Vikstrøm; Anthony D. Fox (Urban Ecosystems, 2023)
Rooks Corvus frugilegus are common and widespread in urban and agricultural habitats in Denmark. Large numbers are killed annually by derogation shooting to control population growth to reduce noise near populated areas and prevent agricultural damage. Responding to increasing public complaints about noise nuisance from urban rookeries, we investigated changes in extent of urban and agricultural habitats within 500 m, 1000 m and 2000 m of all known breeding rook colonies (rookeries) in eastern Jutland, Denmark in 1991 compared to 2021 based on open access land cover GIS layers in 1990 and 2019. Numbers of rookeries increased by 40% from 95 (1991) to 133 (2021) but nest abundance increased only by 6% from 10,299 to 10,887 due to more and significantly smaller rookeries, increasingly associated with urban sites. In both years, the proportion of urban area within distance classes of rookeries was significantly higher, and the area of agriculture significantly lower, than at randomly chosen points in the same region. The proportion of urban area around each rookery decreased with increasing distance, whereas the proportion of agricultural land cover increased. The proportional area of urban land use within the distance classes increased between 1991 and 2021 whereas agricultural land cover decreased. Given no simultaneous major change in overall land use, our results indicate an increasing selection by rooks for smaller urban rookeries over agricultural landscapes, where rookeries have declined. We consider these trends, especially the proliferation of smaller rookeries in urban areas, as a potential explanation for the upsurge in public complaints about rookery noise in residential areas. We urge further research to explain the causes behind these trends before we can provide science-based solutions to resolve such conflicts effectively.

Precipitation buffers temperature‐driven local extinctions of moths at warm range margins - Lisbeth A. Hordley; Richard Fox; Andrew J. Suggitt; Nigel A. D. Bourn (Ecology Letters, 2023)
Species' distributions are moving polewards in response to climate change, and although range expansions of relatively warm‐adapted species are widely reported, reports of range retractions in cool‐adapted species are less common. Here, we analysed species' distribution shifts for 76 cool‐adapted moths in Great Britain using citizen science occurrence records from the National Moth Recording Scheme over a 40‐year period. Although we find evidence for trailing edge shifts to higher latitudes, shifts in species' range centroids are oriented towards the north‐west, and are more closely correlated with directional changes in total precipitation than average temperature. We also found that species' local extinction risk is higher in areas where temperature is high and precipitation is low, but this risk diminishes as precipitation increases. Adaptation efforts should therefore focus on maintaining or increasing water availability as the climate continues to change.

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Effects of compound disturbance on Canada lynx and snowshoe hare: Wildfire and forest management influence timing and intensity of use - Lucretia E. Olson; Justin S. Crotteau; Shelagh Fox; Gary Hanvey; Joseph D. Holbrook; Scott Jackson; John R. Squires (Forest Ecology and Management, 2023)

Long-term aircraft noise exposure and risk of hypertension in postmenopausal women - Daniel D. Nguyen; Eric A. Whitsel; Gregory A. Wellenius; Jonathan I. Levy; Jessica H. Leibler; Stephanie T. Grady; James D. Stewart; Matthew P. Fox; Jason M. Collins; Melissa N. Eliot; Andrew Malwitz; JoAnn E. Manson; et al. (Environmental Research, 2023)

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Effects of long-term ambient air pollution exposure on township-level pulmonary tuberculosis notification rates during 2005–2017 in Ningxia, China - Igor Popovic; Ricardo J. Soares Magalhães; Yurong Yang; Shukun Yang; Boyi Yang; Guanghui Dong; Xiaolin Wei; Greg J. Fox; Melanie S. Hammer; Randall V. Martin; Aaron van Donkelaar; Erjia Ge; et al. (Environmental Pollution, 2023)

Benzodiazepine Shortages: A Recurrent Challenge in Need of a Solution - James D. Whitledge; Erin R. Fox; Maryann Mazer-Amirshahi (Journal of Medical Toxicology, 2023)

Characteristics of extreme daily precipitation events over the Canadian Arctic - Mark C. Serreze; Jessica Voveris; Andrew P. Barrett; Shari Fox; Peter D. Blanken; Alex Crawford (International Journal of Climatology, 2022)
Given growing interest in extreme high‐latitude weather events, we use records from nine meteorological stations and atmospheric reanalysis data to examine extreme daily precipitation events (leading, 99th and 95th percentile) over Arctic Canada. Leading events span 90 mm at Cape Dyer, along the southeast coast of Baffin Island, to 26 mm at Sachs Harbour, on the southwest coast of Banks Island. The 95th percentiles range from 20 to 30% of leading event sizes. Extreme events are most common on or near the month of climatological peak precipitation. Contrasting with Eurasian continental sites having a July precipitation peak corresponding to the seasonal peak in precipitable water, seasonal cycles in precipitation and the frequency of extremes over Arctic Canada are more varied, reflecting marine influences. At Cape Dyer and Clyde River, mean precipitation and the frequency of extremes peak in October when the atmosphere is quickly cooling, promoting strong evaporation from Baffin Bay. At all stations, leading events involved snowfall and strong winds and were associated with cyclone passages (mostly of relatively strong storms). They also involved strong vapour fluxes, sometimes associated with atmospheric rivers or their remnants. The most unusual sequence of events identified here occurred at Clyde River, where the three largest recorded precipitation events occurred in April of 1977. Obtaining first‐hand accounts of this series of events has proven elusive. Identified links between extreme events and atmospheric rivers demonstrates the need to better understand how the characteristics of such features will change in the future.

Lesion network mapping of mania using different normative connectomes - Gonçalo Cotovio; Francisco Faro Viana; Michael D. Fox; Albino J. Oliveira-Maia (Brain Structure and Function, 2022)
Lesion network mapping is a neuroimaging technique that explores the network of regions functionally connected to lesions causing a common syndrome. The technique uses resting state functional connectivity from large databases of healthy individuals, i.e., connectomes, and has allowed for important insight into the potential network mechanisms underlying several neuropsychiatric disorders. However, concerns regarding reproducibility have arisen, that may be due to the use of different connectomes, with variable MRI acquisition parameters and preprocessing methods. Here, we tested the impact of using different connectomes on the results of lesion network mapping for mania. We found results were reliable and consistent independent of the connectome used.

Appraisal of coral bleaching thresholds and thermal projections for the northern Red Sea refugia - Ahmed Eladawy; Takashi Nakamura; Mohamed Shaltout; Asmaa Mohammed; Kazuo Nadaoka; Michael D. Fox; Eslam O. Osman (Frontiers in Marine Science, 2022)
Corals in the northern Red Sea exhibit high thermal tolerance despite the increasing heat stress. It is assumed that corals throughout the Red Sea have similar bleaching thresholds (32°C or higher), and hence greater bleaching tolerance of corals in the northern Red Sea region is likely due to lower ambient water temperatures (25–28°C) that remain well below the corals’ physiological maxima. Whether bleaching patterns across the Red Sea are independent of the local maximum monthly mean of seawater temperature and aligned with an assumed 32°C threshold has yet to be determined. Here, we used remotely sensed surface sea temperature data spanning 1982–2020 to model spatial distributions of Degree Heat Weeks across the Red Sea in relation to assumed coral thermal threshold values of 30, 31, and 32°C. We also used the Coupled Model Intercomparison Project Phase 5 model outputs to predict warming trends in the Red Sea under different greenhouse gas representative concentration pathways (RCPs). We show that applying 32°C thresholds dramatically reduces effective Degree Heat Weeks in the north, but not in central or southern Red Sea regions, a finding that is consistent with historical bleaching observations (1998–2020) throughout the Red Sea. Further, model predictions under the most extreme RCP8.5 scenario exhibited ~3°C warming by the end of the 21 st century throughout the Red Sea with less pronounced warming for the northern Red Sea (2–2.5°C) compared to the central and southern regions (2.7–3.1°C).This warming rate will remain below the assumed thermal threshold for the northern Red Sea which should help this region to serve as refugia (i.e., maintaining favorable temperatures) for corals to persist for decades ahead. Together, our results support the notion that corals have similar thresholds throughout the Red Sea; hence, coral bleaching thresholds are independent of the local maximum monthly mean. Consequently, where regional warming projections suggest the northern Red Sea will not reach assumed bleaching thresholds (32°C) before the end of the 21 st century, coral reefs in the northern region may be among the last standing against climate change.

Exceptional freshening and cooling in the eastern subpolar North Atlantic caused by reduced Labrador Sea surface heat loss - Alan D. Fox; Patricia Handmann; Christina Schmidt; Neil Fraser; Siren Rühs; Alejandra Sanchez-Franks; Torge Martin; Marilena Oltmanns; Clare Johnson; Willi Rath; N. Penny Holliday; Arne Biastoch; et al. (Ocean Science, 2022)
Observations of the eastern subpolar North Atlantic in the 2010s show exceptional freshening and cooling of the upper ocean, peaking in 2016 with the lowest salinities recorded for 120 years. Published theories for the mechanisms driving the freshening include: reduced transport of saltier, warmer surface waters northwards from the subtropics associated with reduced meridional overturning; shifts in the pathways of fresher, cooler surface water from the Labrador Sea driven by changing patterns of wind stress; and the eastward expansion of the subpolar gyre. Using output from a high-resolution hindcast model simulation, we propose that the primary cause of the exceptional freshening and cooling is reduced surface heat loss in the Labrador Sea. Tracking virtual fluid particles in the model backwards from the eastern subpolar North Atlantic between 1990 and 2020 shows the major cause of the freshening and cooling to be an increased outflow of relatively fresh and cold surface waters from the Labrador Sea; with a minor contribution from reduced transport of warmer, saltier surface water northward from the subtropics. The cooling, but not the freshening, produced by these changing proportions of waters of subpolar and subtropical origin is mitigated by reduced along-track heat loss to the atmosphere in the North Atlantic Current. We analyse modelled boundary exchanges and water mass transformation in the Labrador Sea to show that since 2000, while inflows of lighter surface waters remain steady, the increasing output of these waters is due to reduced surface heat loss in the Labrador Sea beginning in the early 2000s. Tracking particles further upstream reveals that the primary source of the increased volume of lighter water transported out of the Labrador Sea is increased recirculation of water, and therefore longer residence times, in the upper 500–1000 m of the subpolar gyre.

Inconsistent results from trait-based analyses of moth trends point to complex drivers of change - George M. Tordoff; Emily B. Dennis; Richard Fox; Patrick M. Cook; Tony M. Davis; Dan Blumgart; Nigel A. D. Bourn (Biodiversity and Conservation, 2022)

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Decadal stability of coral reef benthic communities on Palmyra Atoll, central Pacific, through two bleaching events - Adi Khen; Maggie D. Johnson; Michael D. Fox; Samantha M. Clements; Amanda L. Carter; Jennifer E. Smith (Coral Reefs, 2022)
The prevalence of coral bleaching due to thermal stress has been increasing on coral reefs worldwide. While many studies have documented how corals respond to warming, fewer have focused on benthic community responses over longer time periods or on the response of non-coral taxa (e.g., crustose coralline algae, macroalgae, or turf). Here, we quantify spatial and temporal changes in benthic community composition over a decade using image analysis of permanent photoquadrats on Palmyra Atoll in the central Pacific Ocean. Eighty permanent plots were photographed annually between 2009 and 2018 on both the wave-exposed fore reef (FR, 10 m depth, n = 4 sites) and the wave-sheltered reef terrace (RT, 5 m depth, n = 4 sites) habitats. The El Niño events of 2009–2010 and 2015–2016 resulted in acute thermal stress and coral bleaching was observed at both reef habitats during these events. Across 10 yr and two bleaching events, the benthic community structure on Palmyra shows evidence of long-term stability. Communities on the RT exhibited minimal change in percent cover of the dominant functional groups, while the FR had greater variability and minor declines in hard coral cover. There was also spatial variation in the trajectory of each site through time. Coral cover decreased at some sites 1 yr following both bleaching events and was replaced by different algal groups depending on the site, yet returned to pre-bleaching levels within 2 yr. Overall, our data reveal the resilience of calcifier-dominated coral reef communities on Palmyra Atoll that have persisted over the last decade despite two bleaching events, demonstrating the capacity for these reefs to recover from and/or withstand disturbances in the absence of local stressors.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Chronic Opioid Administration is Associated with Prevotella-dominated Dysbiosis in SIVmac251 Infected, cART-treated Macaques - Samuel D. Johnson; Howard S. Fox; Shilpa Buch; Siddappa N. Byrareddy (Journal of Neuroimmune Pharmacology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Sources and Cycling of Particulate Organic Matter in Baffin Bay: A Multi-Isotope δ13C, δ15N, and Δ14C Approach - Aislinn Fox; Brett D. Walker (Frontiers in Marine Science, 2022)
The Canadian Arctic is warming three times faster than the rest of the planet. The impact of climate change on the Arctic carbon cycle, and in particular for Baffin Bay, remains poorly constrained. Sinking particulate organic matter (POM sink ) is a key component of the biological carbon pump and provides a direct linkage between surface productivity and the preservation of carbon in marine sediments. While POM sink provides a rapid POM shunt to the deep ocean (days) the majority of marine POM is suspended (POM susp ) persists for years in the water column. Stable carbon (δ 13 C), nitrogen (δ 15 N) and radiocarbon (Δ 14 C) measurements are powerful tools for evaluating sources and cycling of POM. In this study, we measure depth-integrated (0-400m) POM susp stable carbon (δ 13 C), nitrogen (δ 15 N) and radiocarbon (Δ 14 C) values at 11 stations in Baffin Bay. We use POM C:N a ratios to evaluate its diagenetic state. POM susp δ 13 C and δ 15 N values ranged from −21.6‰ to −29.5‰, and +3.84‰ to +7.21‰, respectively. POM susp Δ 14 C values ranged from −41.8‰ to +76.8‰. Together, our results suggest Baffin Bay POM susp has multiple carbon and nitrogen sources. POM susp δ 13 C and Δ 14 C are strongly correlated to surface salinity, indicating surface water has a strong influence on POM susp isotopic composition and 14 C-age. POM susp from coastal Greenland stations have similar Δ 14 C values to surface dissolved inorganic carbon (DIC) and POM concentrations, consistent with primary production as the predominant POM susp source in Eastern Baffin Bay. Positive POM susp Δ 14 C values in central Baffin Bay suggest an accumulation of atmospheric “bomb” 14 C in the sub-polar gyre. POM susp exiting Davis Strait via the Baffin Island Current was determined to have a significant degraded, resuspended sediment component. Finally, POM susp δ 15 N values highlight two distinct N sources in Baffin Bay: Pacific and Arctic nutrients at Northern gateway stations vs. the influx of Atlantic nutrients via Davis Strait along coastal Greenland. Overall, these first Baffin Bay POM susp Δ 14 C values provide useful baseline data for rapidly changing Arctic ecosystem.

Annual variation in waterbird clutch initiation date in relation to spring thaw in Arctic Russia - Diana Solovyeva; Daria A. Barykina; Olga D. Prokopenko; Thorsten J. S. Balsby; Anthony D. Fox (International Journal of Biometeorology, 2022)

Traits data for the butterflies and macro‐moths of Great Britain and Ireland - Patrick M. Cook; George M. Tordoff; Tony M. Davis; Mark S. Parsons; Emily B. Dennis; Richard Fox; Marc S. Botham; Nigel A. D. Bourn (Ecology, 2022)
Butterflies and moths, collectively Lepidoptera, are integral components of ecosystems, providing key services such as pollination and a prey resource for vertebrate and invertebrate predators. Lepidoptera are a relatively well studied group of invertebrates. In Great Britain and Ireland numerous citizen science projects provide data on changes in distribution and abundance. The availability of high‐quality monitoring and recording data, combined with the rapid response of Lepidoptera to environmental change, makes them ideal candidates for traits‐based ecological studies. Recently, there has been an increase in the number of studies documenting traits‐based responses of Lepidoptera, highlighting the demand for a standardized and referenced traits database. There is a wide range of primary and secondary literature sources available regarding the ecology of British and Irish Lepidoptera to support such studies. Currently these sources have not been collated into one central repository that would facilitate and enhance future research. Here, we present a comprehensive traits database for the butterflies and macro‐moths of Great Britain and Ireland. The database covers 968 species in 21 families. Ecological traits fall into four main categories: life cycle ecology and phenology, host plant specificity and characteristics, breeding habitat, and morphological characteristics. The database also contains data regarding species distribution, conservation status, and temporal trends for abundance and occupancy. This database can be used for a wide array of purposes including further fundamental research on species and community responses to environmental change, conservation and management studies, and evolutionary biology. There are no copyright restrictions, and this paper must be cited if data are used in publications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Spectroscopic investigation of iron(III) cysteamine dioxygenase in the presence of substrate (analogs): implications for the nature of substrate-bound reaction intermediates - Rebeca L. Fernandez; Nicholas D. Juntunen; Brian G. Fox; Thomas C. Brunold (JBIC Journal of Biological Inorganic Chemistry, 2021)

Do alien predators pose a particular risk to duck nests in Northern Europe? Results from an artificial nest experiment - Sari Holopainen; Veli-Matti Väänänen; Mia Vehkaoja; Anthony D. Fox (Biological Invasions, 2021)
Several alien predator species have spread widely in Europe during the last five decades and pose a potential enhanced risk to native nesting ducks and their eggs. Because predation is an important factor limiting Northern Hemisphere duck nest survival, we ask the question, do alien species increase the nest loss risk to ground nesting ducks? We created 418 artificial duck nests in low densities around inland waters in Finland and Denmark during 2017–2019 and monitored them for seven days after construction using wildlife cameras to record whether alien species visit and prey on the nests more often than native species. We sampled various duck breeding habitats from eutrophic agricultural lakes and wetlands to oligotrophic lakes and urban environments. The results differed between habitats and the two countries, which likely reflect the local population densities of the predator species. The raccoon dog ( Nyctereutes procyonoides ), an alien species, was the most common mammalian nest visitor in all habitats and its occurrence reduced nest survival. Only in wetland habitats was the native red fox ( Vulpes vulpes ) an equally common nest visitor, where another alien species, the American mink ( Neovison vison ), also occurred among nest visitors. Although cautious about concluding too much from visitations to artificial nests, these results imply that duck breeding habitats in Northern Europe already support abundant and effective alien nest predators, whose relative frequency of visitation to artificial nests suggest that they potentially add to the nest predation risk to ducks over native predators.

Views of management effectiveness in tropical reef fisheries - Timothy R. McClanahan; Emily S. Darling; Sangeeta Mangubhai; Georgina G. Gurney; W. Peni Lestari; Margaret Fox; Stacy D. Jupiter; Dhila A. Yulistianti; Nyawira A. Muthiga; Stephanie D’agata (Fish and Fisheries, 2021)
The effectiveness and outcomes of management are expected to improve when people are informed, engaged and influential in governance and management procedures. The social‐ecological and demographic contexts should, however, influence an individual's perceptions and willingness to engage and access appreciable benefits from management. To evaluate how engagement, procedures and perceived outcomes varied with geographic and social‐ecological context, we asked 1582 heads‐of‐households in 38 fishing villages in four tropical countries to evaluate the benefits of their local fisheries management. Responses to 10 collective action, social performance and management procedure questions fell along three response axes, namely (a) the potential benefits of management, (b) resource status and the reliability of yields and (c) the respondents' ability to influence management decisions. Respondents were most positive about the organization of the existing management systems but more sceptical about their ability to influence decision‐making and subsequent yields and resource status. More frequent negative opinions increased with urbanization (distance to cities and population density), which could arise from challenges of group cohesion, local control and subsequent management efficacy. Consequently, we argue that some common rural, decentralized, or collective fisheries management systems are inappropriate for engaging participation in urban contexts. Across all locations, there is a need to increase participation with management decisions and actions, and to transparently evaluate and respond to resource and yield outcomes. Crafting recommendations appropriate for urban contexts will be increasingly relevant as urbanization and commercialized fisheries expand in tropical countries.

Annual survival estimates of Taiga Anser fabalis and Tundra Bean Geese A. serrirostris wintering in The Netherlands, 1967–1987 - Anthony D. Fox; Morten Frederiksen; Thomas Heinicke; Kevin K. Clausen; Henk P. van der Jeugd (Journal of Ornithology, 2021)

Using the Schmahmann Syndrome Scale to Assess Cognitive Impairment in Young Adults with Metabolic Syndrome: a Hypothesis-Generating Report - Eithan Kotkowski; Larry R. Price; Cheasequah J. Blevins; Crystal G. Franklin; Mary D. Woolsey; Ralph A. DeFronzo; John Blangero; Ravindranath Duggirala; David C. Glahn; Jeremy D. Schmahmann; Peter T. Fox (The Cerebellum, 2021)

‘Expedited Interhemispheric Inhibition’: A Simple Method to Collect Additional IHI Data in the Same Amount of Time - Daniel T. Corp; Jason He; Danielle Cooke; Ruben Perellón-Alfonso; Juho Joutsa; Alvaro Pascual-Leone; Michael D. Fox; Christian Hyde (Brain Topography, 2021)

Recent increase in annual survival of nesting female Common Scoter Melanitta nigra in Iceland - Ib K. Petersen; Morten Frederiksen; Aevar Petersen; Hannah J. Robson; Árni Einarsson; Rasmus D. Nielsen; Anne L. Harrison; Anja Cervencl; Anthony D. Fox (Journal of Ornithology, 2021)

Author Correction: Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)

Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)
Purpose of Review Assessment of the impact of ocean resolution in Earth System models on the mean state, variability, and future projections and discussion of prospects for improved parameterisations to represent the ocean mesoscale. Recent Findings The majority of centres participating in CMIP6 employ ocean components with resolutions of about 1 degree in their full Earth System models (eddy-parameterising models). In contrast, there are also models submitted to CMIP6 (both DECK and HighResMIP) that employ ocean components of approximately 1/4 degree and 1/10 degree (eddy-present and eddy-rich models). Evidence to date suggests that whether the ocean mesoscale is explicitly represented or parameterised affects not only the mean state of the ocean but also the climate variability and the future climate response, particularly in terms of the Atlantic meridional overturning circulation (AMOC) and the Southern Ocean. Recent developments in scale-aware parameterisations of the mesoscale are being developed and will be included in future Earth System models. Summary Although the choice of ocean resolution in Earth System models will always be limited by computational considerations, for the foreseeable future, this choice is likely to affect projections of climate variability and change as well as other aspects of the Earth System. Future Earth System models will be able to choose increased ocean resolution and/or improved parameterisation of processes to capture physical processes with greater fidelity.

Evidence of diverse movement strategies and habitat use by white sharks, Carcharodon carcharias, off southern Australia - Russell Bradford; T. A. Patterson; P. J. Rogers; R. McAuley; S. Mountford; C. Huveneers; R. Robbins; A. Fox; B. D. Bruce (Marine Biology, 2020)
Large endothermic pelagic sharks are highly migratory and use habitats spanning a broad range of coastal, neritic and oceanic areas. This study aimed to resolve the current lack of information on the movements and habitat use of white sharks, Carcharodon carcharias , between shelf, slope and oceanic areas located off southwestern Australia. Movement behaviours, spatial distribution patterns and vertical habitat use of juvenile, sub-adult and adult white sharks ranging in size from 1.9 to 5.7 m total length were examined using 43 satellite tags deployed over 15 years. Pop-up satellite archival tags and satellite-linked radio tags collected 3663 days and > 109,900 km of tracking data over periods of up to 381 days. We demonstrated sex-based differences in movement and distribution patterns of male (21) and female (19) white sharks. Female dispersal was broader and extended further offshore than males, which largely remained in neritic and gulf habitats. Female white sharks experienced a narrower range of water temperatures ( F = 9.0–19.0 °C; M = 10.4–24.8 °C). Despite these subtle differences, both sexes showed an affinity to the Neptune Island Group and the shelf slope canyons of the eastern Great Australian Bight, which are productive and oceanographically complex regions that support known prey of white sharks. This study highlighted that the southern-western Australian population of white sharks use off-shelf habitat to a greater extent than previously identified. Findings have potential implications for: ecological risk assessments of fisheries that operate in these offshore habitats and for monitoring and managing marine protected areas.

Advances in Observing and Understanding Small-Scale Open Ocean Circulation During the Gulf of Mexico Research Initiative Era - Eric A. D'Asaro; Daniel F. Carlson; Marcelo Chamecki; Ramsey R. Harcourt; Brian K. Haus; Baylor Fox-Kemper; M. Jeroen Molemaker; Andrew C. Poje; Di Yang (Frontiers in Marine Science, 2020)

Historic development of heavy metal contamination into the Firth of Thames, New Zealand - S. Boehnert; S. Ruiz Soto; B. R. S. Fox; Y. Yokoyama; D. Hebbeln (Geo-Marine Letters, 2020)
Near-coastal marine sediments often provide high-resolution records of various anthropogenic influences such as the release of heavy metals, which pose a potentially negative influence on aquatic ecosystems because of their toxicity and persistence. In places, the gradual onset of man-made heavy metal emission dates back to ~ 4500 years BP and is difficult to distinguish from potential natural sources. New Zealand offers a perfect setting for studies on anthropogenic impact due to its well-defined three-step development: pre-human era (until ~ 1300 CE), Polynesian era (~ 1300–1800 CE) and European era (since ~ 1840 CE). However, hardly any information exists about the degree of heavy metal input to New Zealand’s coastal areas and the ‘pristine’ natural background values. This study determines the natural background contents of lead (Pb) and zinc (Zn) in marine sediments of the Firth of Thames, a shallow marine embayment on New Zealand’s North Island, and investigates anthropogenic inputs in historic times. Eight sediment cores were analysed by X-ray fluorescence (XRF) for their element composition and temporally resolved by a pollen and radiocarbon-based stratigraphic framework. Sharp increases in Pb and Zn contents occurred simultaneously with the onset of goldmining activities (1867 CE) in the nearby catchment area. The contents of Zn (Pb) increase from very stable values around 60 (13) ppm in the older sediments, interpreted to reflect the natural background values, to an average maximum of 160 (60) ppm near the core top, interpreted to reflect a significant anthropogenic input. These findings unravel the history of contamination in the Firth of Thames and provide an urgently needed database for the assessment of its current ecological state.

Status and trends of tundra birds across the circumpolar Arctic - Paul A. Smith; Laura McKinnon; Hans Meltofte; Richard B. Lanctot; Anthony D. Fox; James O. Leafloor; Mikhail Soloviev; Alastair Franke; Knud Falk; Mikhail Golovatin; Vasiliy Sokolov; Aleksandr Sokolov; et al. (Ambio, 2020)
Tundra-breeding birds face diverse conservation challenges, from accelerated rates of Arctic climate change to threats associated with highly migratory life histories. Here we summarise the status and trends of Arctic terrestrial birds (88 species, 228 subspecies or distinct flyway populations) across guilds/regions, derived from published sources, raw data or, in rare cases, expert opinion. We report long-term trends in vital rates (survival, reproduction) for the handful of species and regions for which these are available. Over half of all circumpolar Arctic wader taxa are declining (51% of 91 taxa with known trends) and almost half of all waterfowl are increasing (49% of 61 taxa); these opposing trends have fostered a shift in community composition in some locations. Declines were least prevalent in the African-Eurasian Flyway (29%), but similarly prevalent in the remaining three global flyways (44–54%). Widespread, and in some cases accelerating, declines underscore the urgent conservation needs faced by many Arctic terrestrial bird species.

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marco A. Yáñez; Eric D. Carbaugh; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Trees, 2020)

Caregiver- and Clinician-Reported Adaptive Functioning in Rett Syndrome: a Systematic Review and Evaluation of Measurement Strategies - Eric S. Semmel; Michelle E. Fox; Sabrina D. Na; Rella Kautiainen; Robert D. Latzman; Tricia Z. King (Neuropsychology Review, 2019)

Changes in benthic community composition associated with the outbreak of the corallimorph, Rhodactis howesii, at Palmyra Atoll - Amanda L. Carter; Clinton B. Edwards; Michael D. Fox; Corinne G. Amir; Yoan Eynaud; Maggie D. Johnson; Levi S. Lewis; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Novel ablation technique shows no sperm priming response by male eastern mosquitofish to cues of female availability - Meng-Han Joseph Chung; Michael D. Jennions; Rebecca J. Fox (Behavioral Ecology and Sociobiology, 2019)

Foraging consistency of coral reef fishes across environmental gradients in the central Pacific - Brian J. Zgliczynski; Gareth J. Williams; Scott L. Hamilton; Elisabeth G. Cordner; Michael D. Fox; Yoan Eynaud; Robert H. Michener; Les S. Kaufman; Stuart A. Sandin (Oecologia, 2019)

Opinions of citizen scientists on open access to UK butterfly and moth occurrence data - Richard Fox; Nigel A. D. Bourn; Emily B. Dennis; Richard T. Heafield; Ilya M. D. Maclean; Robert J. Wilson (Biodiversity and Conservation, 2019)

Long‐term declines of European insectivorous bird populations and potential causes - Diana E. Bowler; Henning Heldbjerg; Anthony D. Fox; Maaike de Jong; Katrin Böhning‐Gaese (Conservation Biology, 2019)
Evidence of declines in insect populations has recently received considerable scientific and societal attention. However, the lack of long‐term insect monitoring makes it difficult to assess whether declines are geographically widespread. By contrast, bird populations are well monitored and often used as indicators of environmental change. We compared the population trends of European insectivorous birds with those of other birds to assess whether patterns in bird population trends were consistent with declines of insects. We further examined whether declines were evident for insectivores with different habitats, foraging strata, and other ecological preferences. Bird population trends were estimated for Europe (1990–2015) and Denmark (1990–2016). On average, insectivores declined over the study period (13% across Europe and 28% in Denmark), whereas omnivores had stable populations. Seedeaters also declined (28% across Europe; 34% in Denmark), but this assessment was based on fewer species than for other groups. The effects of insectivory were stronger for farmland species (especially grassland species), for ground feeders, and for cold‐adapted species. Insectivory was associated with long‐distance migration, which was also linked to population declines. However, many insectivores had stable populations, especially habitat generalists. Our findings suggest that the decline of insectivores is primarily associated with agricultural intensification and loss of grassland habitat. The loss of both seed and insect specialists indicates an overall trend toward bird communities dominated by diet generalists.

Transition to lead-free ammunition benefits all - Jon M. Arnemo; Ruth Cromie; Anthony D. Fox; Niels Kanstrup; Rafael Mateo; Deborah J. Pain; Vernon G. Thomas (Ambio, 2019)

Foreword - Niels Kanstrup; Vernon G. Thomas; Anthony D. Fox (Ambio, 2019)

The transition to non-lead sporting ammunition and fishing weights: Review of progress and barriers to implementation - Vernon G. Thomas; Niels Kanstrup; Anthony D. Fox (Ambio, 2019)

Limited coral mortality following acute thermal stress and widespread bleaching on Palmyra Atoll, central Pacific - Michael D. Fox; Amanda L. Carter; Clinton B. Edwards; Yuichiro Takeshita; Maggie D. Johnson; Vid Petrovic; Corinne G. Amir; Enric Sala; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Integrated Observations of Global Surface Winds, Currents, and Waves: Requirements and Challenges for the Next Decade - Ana B. Villas Bôas; Fabrice Ardhuin; Alex Ayet; Mark A. Bourassa; Peter Brandt; Betrand Chapron; Bruce D. Cornuelle; J. T. Farrar; Melanie R. Fewings; Baylor Fox-Kemper; Sarah T. Gille; Christine Gommenginger; et al. (Frontiers in Marine Science, 2019)

Reduction of exposure to tacrolimus trough level variability is associated with better graft survival after kidney transplantation - Ruth Rahamimov; Hagit Tifti-Orbach; Boris Zingerman; Hefziba Green; Shira Schneider; Avry Chagnac; Eytan Mor; Benjamin D. Fox; Benaya Rozen-Zvi (European Journal of Clinical Pharmacology, 2019)

The U.S. Climate Resilience Toolkit: evidence of progress - Edward P. Gardiner; David D. Herring; James F. Fox (Climatic Change, 2019)

Effects of lake restoration on breeding abundance of globally declining common pochard (Aythya ferina L.) - Anthony D. Fox; Thorsten J. S. Balsby; Hans E. Jørgensen; Torben L. Lauridsen; Erik Jeppesen; Martin Søndergaard; Karsten Fugl; Palle Myssen; Preben Clausen (Hydrobiologia, 2019)

Effects of ecological and anthropogenic factors on waterbird abundance at a Ramsar Site in the Yangtze River Floodplain - Yong Zhang; Anthony D. Fox; Lei Cao; Qiang Jia; Changhu Lu; Herbert H. T. Prins; Willem F. de Boer (Ambio, 2019)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

An Efficient Multi-Objective Optimization Method for Use in the Design of Marine Protected Area Networks - Alan D. Fox; David W. Corne; C. Gabriela Mayorga Adame; Jeff A. Polton; Lea-Anne Henry; J. Murray Roberts (Frontiers in Marine Science, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Surface Ocean Dispersion Observations From the Ship-Tethered Aerostat Remote Sensing System - Daniel F. Carlson; Tamay Özgökmen; Guillaume Novelli; Cedric Guigand; Henry Chang; Baylor Fox-Kemper; Jean Mensa; Sanchit Mehta; Erick Fredj; Helga Huntley; A. D. Kirwan; Maristella Berta; et al. (Frontiers in Marine Science, 2018)

Associations between duck harvest, hunting wing ratios and measures of reproductive output in Northern Europe - Sari Holopainen; Thomas Kjær Christensen; Hannu Pöysä; Veli-Matti Väänänen; Jukka Rintala; Anthony D. Fox (European Journal of Wildlife Research, 2018)

Letter to the editor regarding: Sponge Wetlands: restoring functional flood relief to China’s great rivers - Lei Cao; Xin Wang; Anthony D. Fox (Wetlands Ecology and Management, 2018)

Food Habits of Large Nektonic Fishes: Trophic Linkages in Delaware Bay and the Adjacent Ocean - K. W. Able; J. M. Morson; D. A. Fox (Estuaries and Coasts, 2018)

Changes in nesting success and breeding abundance of Spectacled Eiders Somateria fischeri in the Chaun Delta, Chukotka, Russia, 2003–2016 - Diana V. Solovyeva; Sergey L. Vartanyan; Morten Frederiksen; Anthony D. Fox (Polar Biology, 2018)

Biophysical drivers of coral trophic depth zonation - Gareth J. Williams; Stuart A. Sandin; Brian J. Zgliczynski; Michael D. Fox; Jamison M. Gove; Justin S. Rogers; Kathryn A. Furby; Aaron C. Hartmann; Zachary R. Caldwell; Nichole N. Price; Jennifer E. Smith (Marine Biology, 2018)

Trace element and strontium isotopic analysis of Gulf Sturgeon fin rays to assess habitat use - P. J. Allen; R. J. DeVries; D. A. Fox; R. I. Gabitov; W. G. Anderson (Environmental Biology of Fishes, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Moving forward in circles: challenges and opportunities in modelling population cycles - Frédéric Barraquand; Stilianos Louca; Karen C. Abbott; Christina A. Cobbold; Flora Cordoleani; Donald L. DeAngelis; Bret D. Elderd; Jeremy W. Fox; Priscilla Greenwood; Frank M. Hilker; Dennis L. Murray; Christopher R. Stieha; et al. (Ecology Letters, 2017)
Population cycling is a widespread phenomenon, observed across a multitude of taxa in both laboratory and natural conditions. Historically, the theory associated with population cycles was tightly linked to pairwise consumer–resource interactions and studied via deterministic models, but current empirical and theoretical research reveals a much richer basis for ecological cycles. Stochasticity and seasonality can modulate or create cyclic behaviour in non‐intuitive ways, the high‐dimensionality in ecological systems can profoundly influence cycling, and so can demographic structure and eco‐evolutionary dynamics. An inclusive theory for population cycles, ranging from ecosystem‐level to demographic modelling, grounded in observational or experimental data, is therefore necessary to better understand observed cyclical patterns. In turn, by gaining better insight into the drivers of population cycles, we can begin to understand the causes of cycle gain and loss, how biodiversity interacts with population cycling, and how to effectively manage wildly fluctuating populations, all of which are growing domains of ecological research.

The incidence of post-transplant cancer among kidney transplant recipients is associated with the level of tacrolimus exposure during the first year after transplantation - Shelly Lichtenberg; Ruth Rahamimov; Hefziba Green; Benjamin D. Fox; Eytan Mor; Uzi Gafter; Avry Chagnac; Benaya Rozen-Zvi (European Journal of Clinical Pharmacology, 2017)

Seasonal variation in the sex and age composition of the woodcock bag in Denmark - Thomas Kjær Christensen; Anthony D. Fox; Peter Sunde; Jens Peder Hounisen; Liselotte W. Andersen (European Journal of Wildlife Research, 2017)

Key actions towards the sustainable management of European geese - David A. Stroud; Jesper Madsen; Anthony D. Fox (Ambio, 2017)

Crowded skies: Conflicts between expanding goose populations and aviation safety - David R. Bradbeer; Camilla Rosenquist; Thomas Kjær Christensen; Anthony D. Fox (Ambio, 2017)

Balancing ecosystem function, services and disservices resulting from expanding goose populations - Ralph Buij; Theodorus C. P. Melman; Maarten J. J. E. Loonen; Anthony D. Fox (Ambio, 2017)

Why geese benefit from the transition from natural vegetation to agriculture - Anthony D. Fox; Kenneth F. Abraham (Ambio, 2017)

Threatened species to super-abundance: The unexpected international implications of successful goose conservation - Anthony D. Fox; Jesper Madsen (Ambio, 2017)

Non-normal distribution of the top-of-atmosphere satellite optical measurements over calibration sites - Javier Gorroño; Agnieszka Bialek; Paul D. Green; Peter Harris; Tracy Scanlon; Nigel P. Fox; Craig Underwood (International Journal of Remote Sensing, 2016)

First histological examination of a neoplastic lesion from a free‐swimming white shark, Carcharodon carcharias L. - C Huveneers; S Klebe; A Fox; B Bruce; R Robbins; J D Borucinska; R Jones; M Z Michael (Journal of Fish Diseases, 2016)

Cape cormorants decrease, move east and adapt foraging strategies following eastward displacement of their main prey - RJM Crawford; RM Randall; TR Cook; PG Ryan; BM Dyer; R Fox; D Geldenhuys; J Huisamen; C McGeorge; MK Smith; L Upfold; J Visagie; et al. (African Journal of Marine Science, 2016)

Changes in Air Temperature and Precipitation Chemistry Linked to Water Temperature and Acidity Trends in Freshwater Lakes of Cape Cod National Seashore (Massachusetts, USA) - Stephen M. Smith; Sophia E. Fox; Krista D. Lee (Water, Air, & Soil Pollution, 2016)

Behavioral and qEEG effects of the PDE10A inhibitor THPP-1 in a novel rhesus model of antipsychotic activity - Joshua D. Vardigan; Henry S. Lange; Spencer J. Tye; Steven V. Fox; Sean M. Smith; Jason M. Uslaner (Psychopharmacology, 2016)

Should I stay or should I go? Fitness costs and benefits of prolonged parent–offspring and sibling–sibling associations in an Arctic-nesting goose population - Mitch D. Weegman; Stuart Bearhop; Geoff M. Hilton; Alyn J. Walsh; Kaitlin M. Weegman; David J. Hodgson; Anthony David Fox (Oecologia, 2016)

Combining stable hydrogen (δ2H) isotopes and geolocation to assign Scaly-sided Mergansers to moult river catchments - Diana Solovyeva; Keith A. Hobson; Natalia Kharitonova; Jason Newton; James W. Fox; Vsevolod Afansyev; Anthony D. Fox (Journal of Ornithology, 2016)

Geographic variation in hybridization and ecological differentiation between three syntopic, morphologically similar species of montane lizards - M. L. Haines; J. Melville; J. Sumner; N. Clemann; D. G. Chapple; D. Stuart‐Fox (Molecular Ecology, 2016)
To understand factors shaping species boundaries in closely related taxa, a powerful approach is to compare levels of genetic admixture at multiple points of contact and determine how this relates to intrinsic and extrinsic factors, such as genetic, morphological and ecological differentiation. In the Australian Alps, the threatened alpine bog skink Pseudemoia cryodroma co‐occurs with two morphologically and ecologically similar congeners, P. entrecasteauxii and P. pagenstecheri , and all three species are suspected to hybridize. We predicted that the frequency of hybridization should be negatively correlated with genetic divergence, morphological differentiation and microhabitat separation. We tested this hypothesis using a mitochondrial locus, 13 microsatellite loci, morphological and microhabitat data and compared results across three geographically isolated sites. Despite strong genetic structure between species, we detected hybridization between all species pairs, including evidence of backcrossed individuals at the two sites where all three species are syntopic. Hybridization frequencies were not consistently associated with genetic, morphological or ecological differentiation. Furthermore, P. entrecasteauxii and P. pagenstecheri only hybridized at the two sites where they are syntopic with P. cryodroma , but not at the largest site where P. cryodroma was not recorded, suggesting that P. cryodroma may serve as a bridging species. This study reveals the complex dynamics within a three species hybrid zone and provides a baseline for assessing the impact of climate change and anthropogenic habitat modification on future hybridization frequencies.

Lobar distribution in non-cystic fibrosis bronchiectasis predicts bacteriologic pathogen treatment - S. Izhakian; W. G. Wasser; L. Fuks; B. Vainshelboim; B. D. Fox; O. Fruchter; M. R. Kramer (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Early Expression of Parkinson’s Disease-Related Mitochondrial Abnormalities in PINK1 Knockout Rats - Lance M. Villeneuve; Phillip R. Purnell; Michael D. Boska; Howard S. Fox (Molecular Neurobiology, 2016)

Precipitation in the EURO-CORDEX $$0.11^{° }$$ 0 . 11 ∘ and $$0.44^{° }$$ 0 . 44 ∘ simulations: high resolution, high benefits? - A. F. Prein; A. Gobiet; H. Truhetz; K. Keuler; K. Goergen; C. Teichmann; C. Fox Maule; E. van Meijgaard; M. Déqué; G. Nikulin; R. Vautard; A. Colette; et al. (Climate Dynamics, 2016)

Using Ecological Thresholds to Inform Resource Management: Current Options and Future Possibilities - Melissa M. Foley; Rebecca G. Martone; Michael D. Fox; Carrie V. Kappel; Lindley A. Mease; Ashley L. Erickson; Benjamin S. Halpern; Kimberly A. Selkoe; Peter Taylor; Courtney Scarborough (Frontiers in Marine Science, 2015)

Temperature and Residence Time Controls on an Estuarine Harmful Algal Bloom: Modeling Hydrodynamics and Alexandrium fundyense in Nauset Estuary - David K. Ralston; Michael L. Brosnahan; Sophia E. Fox; Krista D. Lee; Donald M. Anderson (Estuaries and Coasts, 2015)

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Maximizing the identification of QTL for pre-harvest sprouting resistance using seed dormancy measures in a white-grained hexaploid wheat population - Sachin Kumar; Ron E. Knox; Fran R. Clarke; Curtis J. Pozniak; Ron M. DePauw; Richard D. Cuthbert; Stephen Fox (Euphytica, 2015)
Pre-harvest sprouting in spring wheat causes significant financial loss to growers throughout the world and sprouting damage can be reduced by growing resistant genotypes. Several genetic factors, especially those related to seed dormancy, are involved in the control of pre-harvest sprouting resistance. The objective of this study was to identify quantitative trait loci (QTL) influencing pre-harvest sprouting resistance from multiple measures of dormancy at multiple germination intervals on seed harvested across multiple environments. A doubled haploid mapping population of 91 individuals derived from a cross of two Canadian white-seeded spring wheat genotypes, SC8021-V2 (pre-harvest sprouting resistant) and AC Karma (moderately susceptible to pre-harvest sprouting) was used for QTL mapping. Daily germination counts were analysed using germination index, germination resistance and percent germination at intervals of 3, 5, 7, 10, 14 and 21 days from spike samples collected from six field and one greenhouse environments in Saskatchewan, Canada. Continuous frequency distributions at certain measure-durations indicated genetic complexity of dormancy segregation in the SC8021-V2/AC Karma cross. Composite interval mapping detected significant ( p ≤ 0.05) QTL associated with resistance to pre-harvest sprouting on all 21 wheat chromosomes. Of the 26 total QTL, six were novel and the rest were detected either at the same marker or overlapping a marker interval reported in other studies. QTL expressed consistently for germination index, germination resistance and percent germination at different germination durations on chromosomes 2B, 4A, 5D and 6D. QTL identified on homoeologous chromosomes 4A, 4B and 4D with chromosome specific molecular variants of SSR marker wmc617 suggest a conserved region for controlling dormancy on group four. The majority of QTL mapped in regions known to contain factors affecting different components of pre-harvest sprouting resistance like seed dormancy, seed coat colour, ABA responsiveness and alpha-amylase activity. This study demonstrated that using multiple measures of seed dormancy at multiple intervals of germination enhanced identification of QTL affecting dormancy in white-seeded hexaploid wheat.

Benchmarking agency and organizational practices in resilience decision making - Sabrina Larkin; Cate Fox-Lent; Daniel A. Eisenberg; Benjamin D. Trump; Sean Wallace; Colin Chadderton; Igor Linkov (Environment Systems and Decisions, 2015)

Microclimate affects landscape level persistence in the British Lepidoptera - Andrew J. Suggitt; Robert J. Wilson; Tom A. August; Richard Fox; Nick J. B. Isaac; Nicholas A. Macgregor; Michael D. Morecroft; Ilya M. D. Maclean (Journal of Insect Conservation, 2015)

The role of the right temporoparietal junction in attention and social interaction as revealed by ALE meta-analysis - S. C. Krall; C. Rottschy; E. Oberwelland; D. Bzdok; P. T. Fox; S. B. Eickhoff; G. R. Fink; K. Konrad (Brain Structure and Function, 2015)

Urinary bisphenol A-glucuronide and postmenopausal breast cancer in Poland - Britton Trabert; Roni T. Falk; Jonine D. Figueroa; Barry I. Graubard; Montserrat Garcia-Closas; Jolanta Lissowska; Beata Peplonska; Stephen D. Fox; Louise A. Brinton (Cancer Causes & Control, 2014)

Erratum to: Multi-region hemispheric specialization differentiates human from nonhuman primate brain function - Hsiao-Ying Wey; Kimberley A. Phillips; D. Reese McKay; Angela R. Laird; Peter Kochunov; M. Duff Davis; David C. Glahn; John Blangero; Timothy Q. Duong; Peter T. Fox (Brain Structure and Function, 2014)

Multi-region hemispheric specialization differentiates human from nonhuman primate brain function - Hsiao-Ying Wey; Kimberley A. Phillips; D. Reese McKay; Angela R. Laird; Peter Kochunov; M. Duff Davis; David C. Glahn; Timothy Q. Duong; Peter T. Fox (Brain Structure and Function, 2014)

Spring ice formation on goose neck collars: effects on body condition and survival in Greenland white-fronted geese Anser albifrons flavirostris - Anthony D. Fox; Alyn J. Walsh; Mitch D. Weegman; Stuart Bearhop; Carl Mitchell (European Journal of Wildlife Research, 2014)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

Shifting to an energy-poor diet for nitrogen? Not the case for wintering herbivorous Lesser White-fronted Geese in China - Xin Wang; Anthony D. Fox; Xuliang Zhuang; Lei Cao; Fanjuan Meng; Peihao Cong (Journal of Ornithology, 2014)

Cellular Interactions and Signaling in neuroAIDS: Emerging Issues Colloquium - Lena Al-Harthi; Shilpa Buch; Jonathan D. Geiger; Howard E. Gendelman; Johnny J. He; Kelly L. Jordan-Sciutto; Dennis L. Kolson; Jay Rappaport; Sabita Roy; Jialin Zheng; Howard S. Fox (Journal of Neuroimmune Pharmacology, 2014)

Heritable changes in regional cortical thickness with age - Francois Chouinard-Decorte; D. Reese McKay; Andrew Reid; Budhachandra Khundrakpam; Lu Zhao; Sherif Karama; Pierre Rioux; Emma Sprooten; Emma Knowles; Jack W. Kent; Joanne E. Curran; Harald H. H. Göring; et al. (Brain Imaging and Behavior, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Influence of age, sex and genetic factors on the human brain - D. Reese McKay; Emma E. M. Knowles; Anderson A. M. Winkler; Emma Sprooten; Peter Kochunov; Rene L. Olvera; Joanne E. Curran; Jack W. Kent; Melanie A. Carless; Harald H. H. Göring; Thomas D. Dyer; Ravi Duggirala; et al. (Brain Imaging and Behavior, 2014)

Changes in age and sex ratios amongst samples of hunter-shot wings from common duck species in Denmark 1982–2010 - Thomas K. Christensen; Anthony D. Fox (European Journal of Wildlife Research, 2014)

Mammographic surveillance in women aged 35–39 at enhanced familial risk of breast cancer (FH02) - D. G. Evans; S. Thomas; J. Caunt; L. Roberts; A. Howell; M. Wilson; R. Fox; D. M. Sibbering; S. Moss; M. G. Wallis; D. M. Eccles; S. Duffy (Familial Cancer, 2014)

Revisions to the derivation of the Australian and New Zealand guidelines for toxicants in fresh and marine waters - M. St. J. Warne; G. E. Batley; O. Braga; J. C. Chapman; D. R. Fox; C. W. Hickey; J. L. Stauber; R. Van Dam (Environmental Science and Pollution Research, 2014)

The benefits of being big: effects of body size on energy budgets of three wintering goose species grazing Carex beds in the Yangtze River floodplain, China - Xin Wang; Yong Zhang; Meijuan Zhao; Lei Cao; Anthony D. Fox (Journal of Ornithology, 2013)

Evaluation of ionic liquids on phototrophic microbes and their use in biofuel extraction and isolation - Katherine S. Lovejoy; Lauren E. Davis; Lisa M. McClellan; Antonietta M. Lillo; John D. Welsh; Emily N. Schmidt; Claire K. Sanders; Alexander J. Lou; David T. Fox; Andrew T. Koppisch; Rico E. Del Sesto (Journal of Applied Phycology, 2013)

QTLs for water absorption and flour yield identified in the doubled haploid wheat population Lang/QT8766 - G. P. Fox; A. Martin; A. M. Kelly; M. W. Sutherland; D. Martin; P. M. Banks; J. Sheppard (Euphytica, 2013)

Rapid climate driven shifts in wintering distributions of three common waterbird species - Aleksi Lehikoinen; Kim Jaatinen; Anssi V. Vähätalo; Preben Clausen; Olivia Crowe; Bernard Deceuninck; Richard Hearn; Chas A. Holt; Menno Hornman; Verena Keller; Leif Nilsson; Tom Langendoen; et al. (Global Change Biology, 2013)
Climate change is predicted to cause changes in species distributions and several studies report margin range shifts in some species. However, the reported changes rarely concern a species' entire distribution and are not always linked to climate change. Here, we demonstrate strong north‐eastwards shifts in the centres of gravity of the entire wintering range of three common waterbird species along the North‐West E urope flyway during the past three decades. These shifts correlate with an increase of 3.8 °C in early winter temperature in the north‐eastern part of the wintering areas, where bird abundance increased exponentially, corresponding with decreases in abundance at the south‐western margin of the wintering ranges. This confirms the need to re‐evaluate conservation site safeguard networks and associated biodiversity monitoring along the flyway, as new important wintering areas are established further north and east, and highlights the general urgency of conservation planning in a changing world. Range shifts in wintering waterbirds may also affect hunting pressure, which may alter bag sizes and lead to population‐level consequences.

Hydro-climatic effects of future land-cover/land-use change in montane mainland southeast Asia - Omer L. Sen; Deniz Bozkurt; John B. Vogler; Jefferson Fox; Thomas W. Giambelluca; Alan D. Ziegler (Climatic Change, 2013)

Autumn survival inferred from wing age ratios: Wigeon juvenile survival half that of adults at best? - Matthieu Guillemain; Anthony D. Fox; Hannu Pöysä; Veli-Matti Väänänen; Thomas Kjær Christensen; Patrick Triplet; Vincent Schricke; Fränzi Korner-Nievergelt (Journal of Ornithology, 2013)

Niche partitioning of feeding microhabitats produces a unique function for herbivorous rabbitfishes (Perciformes, Siganidae) on coral reefs - R. J. Fox; D. R. Bellwood (Coral Reefs, 2013)

Warming winter effects, fat store accumulation and timing of spring departure of Greenland White-fronted Geese Anser albifrons flavirostris from their winter quarters - Anthony D. Fox; Alyn Walsh (Hydrobiologia, 2012)

Earlier spring staging in Iceland amongst Greenland White-fronted Geese Anser albifrons flavirostris achieved without cost to refuelling rates - Anthony D. Fox; Hugh Boyd; Alyn J. Walsh; David A. Stroud; Jens Nyeland; Ruth L. Cromie (Hydrobiologia, 2012)

Intravenous buspirone for the prevention of postoperative nausea and vomiting - Peter Kranke; Kerstin D. Röhm; Pierre Diemunsch; Tong J. Gan; Christian C. Apfel; Leopold Eberhart; Harold S. Minkowitz; Jan Wallenborn; Dominique Chassard; Gilles Lebuffe; Gabriel M. Fox; Martin R. Tramèr (European Journal of Clinical Pharmacology, 2012)

Developing standardized methods for breeding preharvest sprouting resistant wheat, challenges and successes in Canadian wheat - R. M. DePauw; R. E. Knox; A. K. Singh; S. L. Fox; D. G. Humphreys; P. Hucl (Euphytica, 2012)

Response of Elk to Habitat Modification Near Natural Gas Development - Fred Van Dyke; Autumn Fox; Seth M. Harju; Matthew R. Dzialak; Larry D. Hayden-Wing; Jeffrey B. Winstead (Environmental Management, 2012)

Carbon outcomes of major land‐cover transitions in SE Asia: great uncertainties and REDD + policy implications - Alan D. Ziegler; Jacob Phelps; Jia QI Yuen; Edward L. Webb; Deborah Lawrence; Jeff M. Fox; Thilde B. Bruun; Stephen J. Leisz; Casey M. Ryan; Wolfram Dressler; Ole Mertz; Unai Pascual; et al. (Global Change Biology, 2012)
Policy makers across the tropics propose that carbon finance could provide incentives for forest frontier communities to transition away from swidden agriculture (slash‐and‐burn or shifting cultivation) to other systems that potentially reduce emissions and/or increase carbon sequestration. However, there is little certainty regarding the carbon outcomes of many key land‐use transitions at the center of current policy debates. Our meta‐analysis of over 250 studies reporting above‐ and below‐ground carbon estimates for different land‐use types indicates great uncertainty in the net total ecosystem carbon changes that can be expected from many transitions, including the replacement of various types of swidden agriculture with oil palm, rubber, or some other types of agroforestry systems. These transitions are underway throughout Southeast Asia, and are at the heart of REDD + debates. Exceptions of unambiguous carbon outcomes are the abandonment of any type of agriculture to allow forest regeneration (a certain positive carbon outcome) and expansion of agriculture into mature forest (a certain negative carbon outcome). With respect to swiddening, our meta‐analysis supports a reassessment of policies that encourage land‐cover conversion away from these [especially long‐fallow] systems to other more cash‐crop‐oriented systems producing ambiguous carbon stock changes – including oil palm and rubber. In some instances, lengthening fallow periods of an existing swidden system may produce substantial carbon benefits, as would conversion from intensely cultivated lands to high‐biomass plantations and some other types of agroforestry. More field studies are needed to provide better data of above‐ and below‐ground carbon stocks before informed recommendations or policy decisions can be made regarding which land‐use regimes optimize or increase carbon sequestration. As some transitions may negatively impact other ecosystem services, food security, and local livelihoods, the entire carbon and noncarbon benefit stream should also be taken into account before prescribing transitions with ambiguous carbon benefits.

Performance of remote acoustic receivers within a coral reef habitat: implications for array design - J. Q. Welsh; R. J. Fox; D. M. Webber; D. R. Bellwood (Coral Reefs, 2012)

Temporal variation in responses of species to four decades of climate warming - Louise Mair; Chris D. Thomas; Barbara J. Anderson; Richard Fox; Marc Botham; Jane K. Hill (Global Change Biology, 2012)
Many species are expanding at their leading‐edge range boundaries in response to climate warming. Species are known to respond individualistically to climate change, but there has been little consideration of whether responses are consistent over time. We compared responses of 37 southerly distributed British butterflies over two study periods, first between 1970–1982 and 1995–1999 and then between 1995–1999 and 2005–2009, when mean annual temperature increased regionally by 0.03 °C yr −1 (a significant rate of increase) and 0.01 °C yr −1 (a nonsignificant increase) respectively. Our study species might be expected to benefit from climate warming. We measured three responses to climate to investigate this; changes in range margin, distribution area and abundance. In general, the responses of species were inconsistent over time. Species that increased their distribution areas during the first period tended to do so again during the second period, but the relationship was weak. Changes in range margins and abundance were not consistent. In addition, only 5/37 species showed qualitatively similar responses in all three response variables over time (three species increased and two species declined in all variables in both periods). Overall rates of range expansion and distribution area change were significantly greater in the second study period, despite the lower rate of warming, perhaps due to species exploiting climate‐distribution lags remaining from the earlier, warmer period. However, there was a significantly greater decline in abundance during the second study period, so range expansions northwards were not necessarily accompanied by increases in distribution area and/or abundance. Hence, species ranges have been thinning as they have expanded northwards. The idiosyncratic responses of these species likely reflect the balance of climatic and habitat drivers of species distribution and abundance changes.

Simulating Land-Cover Change in Montane Mainland Southeast Asia - Jefferson Fox; John B. Vogler; Omer L. Sen; Thomas W. Giambelluca; Alan D. Ziegler (Environmental Management, 2012)

A genome-wide association study of osteochondritis dissecans in the Thoroughbred - Laura J. Corbin; Sarah C. Blott; June E. Swinburne; Charlene Sibbons; Laura Y. Fox-Clipsham; Maud Helwegen; Tim D. H. Parkin; J. Richard Newton; Lawrence R. Bramlage; C. Wayne McIlwraith; Stephen C. Bishop; John A. Woolliams; et al. (Mammalian Genome, 2012)

Automated Analysis of Fundamental Features of Brain Structures - Jack L. Lancaster; D. Reese McKay; Matthew D. Cykowski; Michael J. Martinez; Xi Tan; Sunil Valaparla; Yi Zhang; Peter T. Fox (Neuroinformatics, 2011)

Using object-based analysis of image data to count birds: mapping of Lesser Flamingos at Kamfers Dam, Northern Cape, South Africa - Geoff Groom; Ib Krag Petersen; Mark D. Anderson; Anthony D. Fox (International Journal of Remote Sensing, 2011)

Recognizing Contemporary Roles of Swidden Agriculture in Transforming Landscapes of Southeast Asia - ALAN D. ZIEGLER; JEFF M. FOX; EDWARD L. WEBB; CHRISTINE PADOCH; STEVE J. LEISZ; ROB A. CRAMB; OLE MERTZ; THILDE B. BRUUN; TRAN DUC VIEN (Conservation Biology, 2011)

Comparison of isoniazid monoresistant tuberculosis with drug-susceptible tuberculosis and multidrug-resistant tuberculosis - L. Fox; M. R. Kramer; I. Haim; R. Priess; A. Metvachuk; D. Shitrit (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Body mass loss amongst moulting Pochard Aythya ferina and Tufted Duck A. fuligula at Abberton Reservoir, South East England - Anthony D. Fox; Roy King (Journal of Ornithology, 2011)

Rapid Evolution of Lifespan in a Novel Environment: Sex-Specific Responses and Underlying Genetic Architecture - Charles W. Fox; James D. Wagner; Sara Cline; Frances Ann Thomas; Frank J. Messina (Evolutionary Biology, 2011)

Diversity in destinations, routes and timing of small adult and sub‐adult striped bass Morone saxatilis on their southward autumn migration - M. E. Mather; J. T. Finn; S. M. Pautzke; D. Fox; T. Savoy; H. M. Brundage; L. A. Deegan; R. M. Muth (Journal of Fish Biology, 2010)
Almost three‐quarters of the 46 young adult and sub‐adult striped bass Morone saxatilis that were acoustically tagged in Plum Island Estuary, Massachusetts, U.S.A., in the summer of 2006 were detected in one or more southern coastal arrays during their autumn migration. On the basis of the trajectories along which these M. saxatilis moved from feeding to overwintering areas, three migratory groups emerged. After leaving Plum Island Estuary, about half of the fish were detected only in a mid‐latitude array, Long Island Sound. The other half of the tagged fish were detected during autumn and winter in a more southern array, the Delaware Estuary. This latter group of fish may have used two routes. Some travelled to the Delaware Estuary through Long Island Sound while other fish may have taken a second, more direct, coastal route that did not include Long Island Sound. Consequently, a seemingly homogeneous group of fish tagged at the same time in the same non‐natal feeding location exhibited a diversity of southward movement patterns that could affect population‐level processes. These three groups that differed in overwintering location and migration route could be movement contingents with migratory connectivity.

Few data but many fish: marine small-scale fisheries catches for Mozambique and Tanzania - J Jacquet; H Fox; H Motta; A Ngusaru; D Zeller (African Journal of Marine Science, 2010)

Anatomical Global Spatial Normalization - Jack L. Lancaster; Matthew D. Cykowski; David Reese McKay; Peter V. Kochunov; Peter T. Fox; William Rogers; Arthur W. Toga; Karl Zilles; Katrin Amunts; John Mazziotta (Neuroinformatics, 2010)

Diet composition and consumption rate in round goby (Neogobius melanostomus) in its expansion phase in the Trent River, Ontario - Graham D. Raby; Lee F. G. Gutowsky; Michael G. Fox (Environmental Biology of Fishes, 2010)

Conservation genetics of the alligator snapping turtle: cytonuclear evidence of range-wide bottleneck effects and unusually pronounced geographic structure - A. A. Echelle; J. C. Hackler; J. B. Lack; S. R. Ballard; J. Roman; S. F. Fox; D. M. Leslie; R. A. Van Den Bussche (Conservation Genetics, 2010)

Comparison of defined culture systems for feeder cell free propagation of human embryonic stem cells - Veronika Akopian; Peter W. Andrews; Stephen Beil; Nissim Benvenisty; Jennifer Brehm; Megan Christie; Angela Ford; Victoria Fox; Paul J. Gokhale; Lyn Healy; Frida Holm; Outi Hovatta; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

How many juvenile Teal Anas crecca reach the wintering grounds? Flyway-scale survival rate inferred from wing age-ratios - Matthieu Guillemain; Jean-Maxime Bertout; Thomas Kjær Christensen; Hannu Pöysa; Veli-Matti Väänänen; Patrick Triplet; Vincent Schricke; Anthony D. Fox (Journal of Ornithology, 2010)

Planning Future Strategies for Domestic and International NeuroAIDS Research, July 24–25, 2008 - Jeymohan Joseph; David Clifford; Steven D. Douglas; Howard Fox; Howard E. Gendelman; Francisco Gonzalez-Scarano; Igor Grant; Eugene Major; Justin McArthur (Journal of Neuroimmune Pharmacology, 2009)

Genetic architecture underlying convergent evolution of egg-laying behavior in a seed-feeding beetle - Charles W. Fox; James D. Wagner; Sara Cline; Frances Ann Thomas; Frank J. Messina (Genetica, 2009)

Host specificity of Ischnodemus variegatus, an herbivore of West Indian marsh grass (Hymenachne amplexicaulis) - Rodrigo Diaz; William A. Overholt; James P. Cuda; Paul D. Pratt; Alison Fox (BioControl, 2009)

Host specificity of Ischnodemus variegatus, an herbivore of West Indian marsh grass (Hymenachne amplexicaulis) - Rodrigo Diaz; William A. Overholt; James P. Cuda; Paul D. Pratt; Alison Fox (BioControl, 2009)

Remote video bioassays reveal the potential feeding impact of the rabbitfish Siganus canaliculatus (f: Siganidae) on an inner-shelf reef of the Great Barrier Reef - R. J. Fox; D. R. Bellwood (Coral Reefs, 2008)

Reducing fish losses to cormorants using artificial fish refuges: an experimental study - I. RUSSELL; D. PARROTT; M. IVES; D. GOLDSMITH; S. FOX; D. CLIFTON‐DEY; A. PRICKETT; T. DREW (Fisheries Management and Ecology, 2008)
The hypothesis that the introduction of artificial refuges might provide protection for fish and reduce the level of cormorant predation was tested in two, paired‐pond, cross‐over trials during the winters of 2003 and 2004, using a ‘refuge’ pond and an adjacent equivalently stocked ‘control’ pond. There were 77% fewer cormorant visits to the refuge pond than the control pond, on average. There was also a 67% fall in the mean mass of fish consumed per cormorant visit and 79% less fish mass lost in the refuge pond. The results are discussed in the context of interactions between cormorants and fish and the potential use of the tool in fisheries management.

Minimization of potential hERG liability in histamine H3 receptor antagonists - L. A. Black; H. Liu; G. J. Diaz; G. B. Fox; K. E. Browman; J. Wetter; K. C. Marsh; T. R. Miller; T. A. Esbenshade; J. Brioni; M. D. Cowart (Inflammation Research, 2008)

Is fecundity in plaice ( Pleuronectes platessa L.) down‐regulated in response to reduced food intake during autumn? - J. Kennedy; P. R. Witthames; R. D. M. Nash; C. J. Fox (Journal of Fish Biology, 2008)
The effect of controlling food intake during the autumn, which is the time of late vitellogenesis, on fecundity, atresia and follicle and ovary growth was examined for plaice Pleuronectes platessa . Eighteen fish were kept in individual pens and either fed on a high or low ration diet. Fish which increased in whole body condition exhibited an increase in carcass condition which means that when food intake is sufficient to maintain whole body condition some resources are used as storage. Follicle growth rate was positively correlated with change in Fulton’s condition and total atresia was negatively correlated with change in Fulton’s condition. Thus, the rate of vitellogenesis was dependent on the availability of an exogenous food source. Fecundity at the end of the experiment was positively correlated with mass and total length. Food intake had no effect on relative fecundity; however, fish which had a lower food intake lost mass and had a greater intensity of atresia, lowering their absolute fecundity. One fish in a very low condition at the start of the experiment skipped spawning and one fish exhibited a decrease in average follicle diameter during the experiment which is hypothesized to be a prelude to mass atresia.

Microsatellite mapping of adult-plant leaf rust resistance gene Lr22a in wheat - Colin W. Hiebert; Julian B. Thomas; Daryl J. Somers; Brent D. McCallum; Stephen L. Fox (Theoretical and Applied Genetics, 2007)

Microsatellite mapping of adult-plant leaf rust resistance gene Lr22a in wheat - Colin W. Hiebert; Julian B. Thomas; Daryl J. Somers; Brent D. McCallum; Stephen L. Fox (Theoretical and Applied Genetics, 2007)

Minimal intra-seasonal dietary overlap of barnacle and pink-footed geese on their breeding grounds in Svalbard - A. D. Fox; E. Bergersen; I. M. Tombre; J. Madsen (Polar Biology, 2007)

A new family of histamine H3 receptor antagonists based on a natural product: discovery, SAR, and properties of the series - M. Cowart; M. Sun; C. Zhao; D. G. Witte; T. R. Miller; K. M. Krueger; K. Browman; G. B. Fox; Y. L. Bennani; T. A. Esbenshade; A. A. Hancock (Inflammation Research, 2007)

Spring feeding by pink‐footed geese reduces carbon stocks and sink strength in tundra ecosystems - RENÉ Van Der WAL; SOFIE SJÖGERSTEN; SARAH J. WOODIN; ELISABETH J. COOPER; INGIBJÖRG S. JÓNSDÓTTIR; DRIES KUIJPER; TONY A. D. FOX; A. D. HUISKES (Global Change Biology, 2007)
Tundra ecosystems are widely recognized as precious areas and globally important carbon (C) sinks, yet our understanding of potential threats to these habitats and their large soil C store is limited. Land‐use changes and conservation measures in temperate regions have led to a dramatic expansion of arctic‐breeding geese, making them important herbivores of high‐latitude systems. In field experiments conducted in high‐Arctic Spitsbergen, Svalbard, we demonstrate that a brief period of early season belowground foraging by pink‐footed geese is sufficient to strongly reduce C sink strength and soil C stocks of arctic tundra. Mechanisms are suggested whereby vegetation disruption due to repeated use of grubbed areas opens the soil organic layer to erosion and will thus lead to progressive C loss. Our study shows, for the first time, that increases in goose abundance through land‐use change and conservation measures in temperate climes can dramatically affect the C balance of arctic tundra.

Can Hypoxia Tolerance Explain Differences in Distribution of Two Co-Occurring North Temperate Sunfishes? - Michelle Farwell; Michael G. Fox; Christopher D. Moyes; Gary Burness (Environmental Biology of Fishes, 2006)

Perceived Barriers to Integrating Social Science and Conservation - HELEN E. FOX; CAROLINE CHRISTIAN; J. CULLY NORDBY; OLIVER R. W. PERGAMS; GARRY D. PETERSON; CHRISTOPHER R. PYKE (Conservation Biology, 2006)

Temperature‐dependent development rates of cod Gadus morhua eggs - A. J. Geffen; C. J. Fox; R. D. M. Nash (Journal of Fish Biology, 2006)
Temperature development relationships were determined for batches of Irish Sea cod Gadus morhua eggs incubated in flow‐through incubators. Hatching began 16·4 days after fertilization (DAF) at 6° C, 10·3 DAF at 8° C, 9·4 DAF at 10° C and 7·4 DAF at 12° C. Egg mortality increased at the higher temperatures, but survival was >80%. Results were compared with published data at four comparable stage end points: the end of blastula, the end of gastrula, the point of growth of the embryo completely surrounding the yolk and the point when 50% of the eggs were hatched. All the studies showed a curvilinear relationship between age at stage and temperature. There was a 12 day inter‐study difference in time to 50% hatch at 2° C and 4 day difference at 10° C. There were no consistent trends that differentiated eastern v. western, or northern v. southern populations. A single model for cod egg incubation time from fertilization to 50% hatch was derived based on data from six cod populations, but it is recommended that individual stock relationships should be used where possible.

Differential expression of the cardiac ryanodine receptor in normal and arrhythmogenic right ventricular cardiomyopathy canine hearts - Kathryn M. Meurs; Veronique A. Lacombe; Keith Dryburgh; Philip R. Fox; Peter R. Reiser; Mark D. Kittleson (Human Genetics, 2006)

Impacts of climate warming and habitat loss on extinctions at species' low‐latitude range boundaries - ALDINA M. A. FRANCO; JANE K. HILL; CLAUDIA KITSCHKE; YVONNE C. COLLINGHAM; DAVID B. ROY; RICHARD FOX; BRIAN HUNTLEY; CHRIS D. THOMAS (Global Change Biology, 2006)
Polewards expansions of species' distributions have been attributed to climate warming, but evidence for climate‐driven local extinctions at warm (low latitude/elevation) boundaries is equivocal. We surveyed the four species of butterflies that reach their southern limits in Britain. We visited 421 sites where the species had been recorded previously to determine whether recent extinctions were primarily due to climate or habitat changes. Coenonympha tullia had become extinct at 52% of study sites and all losses were associated with habitat degradation. Aricia artaxerxes was extinct from 50% of sites, with approximately one‐third to half of extinctions associated with climate‐related factors and the remainder with habitat loss. For Erebia aethiops (extinct from 24% of sites), approximately a quarter of the extinctions were associated with habitat and three‐quarters with climate. For Erebia epiphron , extinctions (37% of sites) were attributed mainly to climate with almost no habitat effects. For the three species affected by climate, range boundaries retracted 70–100 km northwards ( A. artaxerxes , E. aethiops ) and 130–150 m uphill ( E. epiphron ) in the sample of sites analysed. These shifts are consistent with estimated latitudinal and elevational temperature shifts of 88 km northwards and 98 m uphill over the 19‐year study period. These results suggest that the southern/warm range margins of some species are as sensitive to climate change as are northern/cool margins. Our data indicate that climate warming has been of comparable importance to habitat loss in driving local extinctions of northern species over the past few decades; future climate warming is likely to jeopardize the long‐term survival of many northern and mountain species.

The importance of individual behaviour for successful settlement of juvenile plaice ( Pleuronectes platessa L.): a modelling and field study in the eastern Irish Sea - C. J. FOX; P. MCCLOGHRIE; E. F. YOUNG; R. D. M. NASH (Fisheries Oceanography, 2006)
To study the transport of plaice ( Pleuronectes platessa L.) eggs and larvae in the eastern Irish Sea, we constructed a 3D‐baroclinic physical model and coupled it to a particle‐tracking scheme that allowed aspects of larval behaviour to be simulated. Starting positions for eggs were based upon data from a series of ichthyoplankton surveys and final positions were compared with results of settled plaice distributions from two beam trawl surveys conducted on beaches around the eastern Irish Sea. If simulated larval behaviour was limited to passive drift or horizontal swimming, the particles diffused away from the spawning areas but failed to reach nursery grounds in significant numbers (85–90% remaining offshore). In contrast, switching on circatidal vertical swimming significantly increased the numbers of larvae reaching the coast (only 23–30% remained offshore). Particles tended to accumulate in bays and estuaries and this pattern compared well with the distribution of settled plaice from the field surveys. Studies in the southern North Sea (where spawning and nursery grounds are widely separated) have also demonstrated the importance of selective tidal stream transport for successful recruitment of settling plaice to nursery grounds. Although our understanding of the ontogeny of this behaviour is still poor, the model results presented suggest that this aspect of behaviour is a key factor influencing plaice settlement success.

Travelling to breed - Rudolf H. Drent; Anthony D. Fox; Julia Stahl (Journal of Ornithology, 2006)

Contrasting demographies and persistence of rare annual plants in highly variable environments - Laurel R. Fox; Heather N. Steele; Karen D. Holl; Margaret H. Fusari (Plant Ecology, 2006)

Tree Performance and Root-Zone Salt Accumulation in Three Dryland Australian Plantations - Robert D. Archibald; Richard J. Harper; John E. D. Fox; Richard P. Silberstein (Agroforestry Systems, 2006)

The distributions of a wide range of taxonomic groups are expanding polewards - RACHAEL HICKLING; DAVID B. ROY; JANE K. HILL; RICHARD FOX; CHRIS D. THOMAS (Global Change Biology, 2006)
Evidence is accumulating of shifts in species' distributions during recent climate warming. However, most of this information comes predominantly from studies of a relatively small selection of taxa (i.e., plants, birds and butterflies), which may not be representative of biodiversity as a whole. Using data from less well‐studied groups, we show that a wide variety of vertebrate and invertebrate species have moved northwards and uphill in Britain over approximately 25 years, mirroring, and in some cases exceeding, the responses of better‐known groups.

The Anthracen-9-ylmethyloxy Unit: An Underperforming Motif Within the Fluorescent PET (Photoinduced Electron Transfer) Sensing Framework - David C. Magri; John F. Callan; A. Prasanna de Silva; David B. Fox; Nathan D. McClenaghan; K. R. A. Samankumara Sandanayake (Journal of Fluorescence, 2005)

Strategic approach to mitigating weather induced defects of wheat quality - F. R. Clarke; J. M. Clarke; R. M. DePauw; M. R. Fernandez; S. Fox; J. Gilbert; G. Humphreys; R. E. Knox; T. N. McCaig; D. Procunier; M. Sissons; D. Somers (Euphytica, 2005)

Impact of predation on establishment of the soybean aphid, Aphis glycines in soybean, Glycine max - Tyler B. Fox; Douglas A. Landis; Fernando F. Cardoso; Christina D. Difonzo (BioControl, 2005)

A frequent toll-like receptor (TLR)-2 polymorphism is a risk factor for coronary restenosis - Lutz Hamann; Abuzeid Gomma; Nicolas W. J. Schröder; Cordula Stamme; Christiane Glaeser; Susanne Schulz; Michael Gross; Stefan D. Anker; Kim Fox; Ralf R. Schumann (Journal of Molecular Medicine, 2005)

Effects of agricultural change on abundance, fitness components and distribution of two arctic‐nesting goose populations - A. D. Fox; J. Madsen; H. Boyd; E. Kuijken; D. W. Norriss; I. M. Tombre; D. A. Stroud (Global Change Biology, 2005)
Intensification of agriculture since the 1950s has enhanced the availability, competitive ability, crude protein content, digestibility and extended growing seasons of forage grasses. Spilled cereal grain also provides a rich food source in autumn and in winter. Long‐distance migratory herbivorous geese have rapidly exploited these feeding opportunities and most species have shown expansions in range and population size in the last 50 years. Results of long‐term studies are presented from two Arctic‐breeding populations, the Svalbard pink‐footed goose and the Greenland white‐fronted goose (GWFG). GWFGs have shown major habitat shifts since the 1950s from winter use of plant storage organs in natural wetlands to feeding on intensively managed farmland. Declines in local density on, and abandonment of, unmodified traditional wintering habitat and increased reproductive success among those birds wintering on farmland suggest that density‐dependent processes were not the cause of the shift in this winter‐site‐faithful population. Based on enhanced nutrient and energy intake rates, we argue that observed shifts in both species from traditionally used natural habitats to intensively managed farmland on spring staging and wintering areas have not necessarily been the result of habitat destruction. Increased food intake rates and potential demographic benefits resulting from shifts to highly profitable foraging opportunities on increasingly intensively managed farmland, more likely explain increases in goose numbers in these populations. The geographically exploratory behaviour of subdominant individuals enables the discovery and exploitation of new winter feeding opportunities and hence range expansion. Recent destruction of traditional habitats and declines in farming at northern latitudes present fresh challenges to the well being of both populations. More urgently, Canada geese colonizing breeding and moulting habitats of white‐fronted geese in Greenland are further affecting their reproductive output.

2. Histaminergic mechanisms in the CNS - G. B. Fox; T. A. Esbenshade; J. B. Pan; K. E. Browman; M. Zhang; M. E. Ballard; R. J. Radek; H. Miner; R. S. Bitner; K. M. Krueger; B. B. Yao; R. Faghih; et al. (Inflammation Research, 2005)

Solution structure of T4moC, the Rieske ferredoxin component of the toluene 4-monooxygenase complex - Lars Skjeldal; Francis C. Peterson; Jurgen F. Doreleijers; Luke A. Moe; Jeremie D. Pikus; William M. Westler; John L. Markley; Brian F. Volkman; Brian G. Fox (JBIC Journal of Biological Inorganic Chemistry, 2004)

Retinal and extraocular cytomegalovirus end-organ disease in HIV-infected patients in Europe: a EuroSIDA study, 1994?2001 - I. Yust; Z. Fox; M. Burke; A. Johnson; D. Turner; A. Mocroft; C. Katlama; B. Ledergerber; P. Reiss; O. Kirk (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Structure-activity relationships of A-331440: a new histamine-3 antagonist with anti-obesity properties - Y. L. Bennani; A. A. Hancock; K. M. Krueger; B. B. Yao; G. B. Fox; T. M. Miller; D. G. Witte; R. Faghih; C. H. Kang; M. Cowart; T. A. Esbenshade (Inflammation Research, 2004)

Cognition enhancing effects of novel H 3 receptor (H 3 R) antagonists in several animal models - G. B. Fox; J. B. Pan; A. M. Lewis; K. E. Browman; V. A. Komater; M. J. Buckley; P. Curzon; R. J. Radek; R. Faghih; T. A. Esbenshade; M. D. Cowart; M. W. Decker; et al. (Inflammation Research, 2004)

The Role of Soil Surface Crusting in Desertification and Strategies to Reduce Crusting - D. M. Fox; R. B. Bryan; A. G. Price (Environmental Monitoring and Assessment, 2004)

Genes encoding a fructose-1,6-bisphosphate aldolase and a fructose-1,6-bisphosphatase are present within the gene cluster for mimosine degradation in Rhizobium sp. strain TAL1145 - J. D. Awaya; P. M. Fox; D. Borthakur (Plant and Soil, 2003)

Expression of Barstar as a selectable marker in yeast mitochondria - H. Mireau; N. Arnal; T. D. Fox (Molecular Genetics and Genomics, 2003)

N-Isotope effects on the Raman spectra of Fe2S2 ferredoxin and Rieske ferredoxin: evidence for structural rigidity of metal sites - Frederik A. Rotsaert; Jeremie D. Pikus; Brian G. Fox; John L. Markley; Joann Sanders-Loehr (JBIC Journal of Biological Inorganic Chemistry, 2003)

Common 5S rRNA Variants Are Likely To Be Accepted in Many Sequence Contexts - Zhengdong Zhang; Lisa M. D'Souza; Youn-Hyung M. Lee; George E. Fox (Journal of Molecular Evolution, 2003)

Changes to plant species richness in forest fragments: fragment age, disturbance and fire history may be as important as area - Karen A. Ross; Barry J. Fox; Marilyn D. Fox (Journal of Biogeography, 2002)
Aim The impact of fragmentation on a eucalypt forest was investigated by examining the effects of fragment size, time since fragmentation, degree of anthropogenic disturbance to fragment interiors, and time since fire, on native and exotic plant species richness per unit area. Location Two areas of dry open‐forest were studied on the central coast of New South Wales in south‐eastern Australia. Fifty forest fragments were located at Tomago, an area progressively fragmented over the last 60 years, most recently by clearing for sand‐mining. Also at Tomago were six very large blocks of forest that were used as reference sites. The second area at Myall Lakes National Park (50 km north of Tomago) had four very large areas of intact forest that were also used as reference sites. Methods Fragments were allocated into (1) three size classes: small ( 100 ha). Mean plant species richness per 25 m 2 area was determined for each fragment and analysed separately for native and exotic species. Results The most significant effects observed resulted from anthropogenic disturbance. In fragments with major disturbance, native species richness per unit area was significantly reduced in small‐sized young and medium‐sized old fragments. A significant increase was also observed for exotic species richness in fragments with major disturbance. With minor disturbance, native species richness in small fragments declined significantly with time since fragmentation, in contrast to medium and large fragments. Among recently created fragments, those recently burned had significantly more native species per unit area than those burned 10 or more years ago. Main conclusions Anthropogenic disturbance coupled with fragmentation had a stronger and more immediate effect in reducing native species richness and increasing exotic species richness than did fragmentation alone. In the absence of major disturbance, small fragments had fewer native species than larger size classes, but only after 10 or more years since fragmentation, confirming the importance of controlling for age of fragments when examining species–area relationships. This study has not tested whether differences in area were the direct cause of this loss of species over time; other factors that are correlated with area (such as edge effects) may also be involved. The increase in native species richness following fire was consistent with other studies of fire in unfragmented eucalypt forest. This study thus shows that in addition to the factors emphasized in classical island biogeography models, fragment age, disturbance and fire history are important in explaining species richness in fragmented eucalypt forests.

Operational Altimeter Sea Level Products - G. Jacobs; C. Barron; D. Fox; K. Whitmer; S. Klingenberger; D. May; J. Blaha (Oceanography, 2002)

Microbial Detection with Low Molecular Weight RNA - Katerina D. Kourentzi; George E. Fox; Richard C. Willson (Current Microbiology, 2001)

Impacts of landscape structure on butterfly range expansion - J.K. Hill; Y.C. Collingham; C.D. Thomas; D.S. Blakeley; R. Fox; D. Moss; B. Huntley (Ecology Letters, 2001)
Since the 1940s, the distributions of several butterfly species have been expanding in northern Europe, probably in response to climate warming. We focus on the speckled wood butterfly Pararge aegeria in order to determine impacts of habitat availability on expansion rates. We analyse observed expansion rates since 1940 and also use a spatially explicit mechanistic model (MIGRATE) to simulate range expansion in two areas of the UK which differ in their distribution of breeding habitat (woodland). Observed and simulated expansion rates were in very close agreement but were 42%–45% slower in an area that had 24% less woodland. Unlike P. aegeria , the majority of butterfly species are not currently expanding, almost certainly because of lack of suitable habitat. Incorporating the spatial distribution of habitat into investigations of range changes is likely to be important in determining those species that can and cannot expand, and for predicting potential future range changes.

Leaf abscission phenology of a scrub oak: consequences for growth and survivorship of a leaf mining beetle - Kim J. Waddell; Charles W. Fox; Kenneth D. White; Timothy A. Mousseau (Oecologia, 2001)

Expression of Marker RNAs in Pseudomonas putida - Lisa M. D'Souza; Richard C. Willson; George E. Fox (Current Microbiology, 2000)

Factors determining mammal species richness on habitat islands and isolates: habitat diversity, disturbance, species interactions and guild assembly rules - Barry J. Fox; Marilyn D. Fox (Global Ecology and Biogeography, 2000)
For over three decades the equilibrium theory of island biogeography has galvanized studies in ecological biogeography. Studies of oceanic islands and of natural habitat islands share some similarities to continental studies, particularly in developed regions where habitat fragmentation results from many land uses. Increasingly, remnant habitat is in the form of isolates created by the clearing and destruction of natural areas. Future evolution of a theory to predict patterns of species abundance may well come from the application of island biogeography to habitat fragments or isolates. In this paper we consider four factors other than area and isolation that influence the number and type of mammal species coexisting in one place: habitat diversity, habitat disturbance, species interactions and guild assembly rules. In all examples our data derive from mainland habitat, fragmented to differing degrees, with different levels of isolation. Habitat diversity is seen to be a good predictor of species richness. Increased levels of disturbance produce a relatively greater decrease in species richness on smaller than on larger isolates. Species interactions in the recolonization of highly disturbed sites, such as regenerating mined sites, is analogous to island colonization. Species replacement sequences in secondary successions indicate not just how many, but which species are included. Lastly, the complement of species established on islands, or in insular habitats, may be governed by guild assembly rules. These contributions may assist in taking a renewed theory into the new millennium.

The origin and distribution of nitrate in groundwater from village wells in Kotagede, Yogyakarta, Indonesia - Geoffrey D. Smith; Robbert Wetselaar; James J. Fox; Robert H. M. van de Graaff; Doeljachman Moeljohardjo; Joko Sarwono; Wiranto; Sri Rahajoe Asj'ari; Suharto Tjojudo; Basuki (Hydrogeology Journal, 1999)

Altered responses to potassium in cerebellar neurons from weaver heterozygote mice - A. P. Fox; S. Dlouhy; B. Ghetti; J. H. Hurley; P. G. P. Nucifora; D. J. Nelson; L. Won; A. Heller (Experimental Brain Research, 1998)

The effects of simulated spring goose grazing on the growth rate and protein content of Phleum pratense leaves - A. D. Fox; Jens N. Kristiansen; David A. Stroud; Hugh Boyd (Oecologia, 1998)

Metabolic Conversion of 1,1-Dichloro-2,2- bis ( p -chlorophenyl)ethane (DDD) to 1,1-Dichloro-2,2- bis ( p -chlorophenyl)ethylene (DDE) in the Male F344/NCr Rat - S. D. Fox; J. M. Roman; H. J. Issaq; R. W. Nims (Archives of Environmental Contamination and Toxicology, 1998)

Upscaling a simple erosion model from small areas to a large region - D. King; D.M. Fox; J. Daroussin; Y. Le Bissonnais; V. Danneels (Nutrient Cycling in Agroecosystems, 1998)

Characterization of ‘Sun II’ oat monosomics through C-banding and identification of eight new ‘Sun II’ monosomics - E. N. Jellen; H. W. Rines; S. L. Fox; D. W. Davis; R. L. Phillips; B. S. Gill (Theoretical and Applied Genetics, 1997)

High-density populations of diamondback moth have broader host-plant diets - D. S. Bigger; L. R. Fox (Oecologia, 1997)

Basking shark occurrence off south‐west England in relation to zooplankton abundance - D. W. Sims; A. M. Fox; D. A. Merrett (Journal of Fish Biology, 1997)
Basking sharks Cetorhinus maximus >3 m total length arrived off Plymouth, U.K. directly after the increase in zooplankton density in May, while young‐of‐the‐year basking sharks ( −3 ). No basking sharks were seen after July when the zooplankton density was least.

Suppression of PLRV Titer in transgenic Russet Burbank and Ranger Russet - Charles R. Brown; Oney P. Smith; V. D. Damsteegt; Ching-Pa Yang; Lee Fox; P. E. Thomas (American Journal of Potato Research, 1995)

Tfm Lac: A second isolation of testicular feminization in mice - J. A. Politch; T. O. Fox; P. Houben; L. Bullock; D. Lovell (Biochemical Genetics, 1988)

Purification of human leukocyte interferon alpha by Carboxymethyl Controlled Pore Glass bead chromatography - I. Mecs; D. Chin; F. Fox; Mathilde Krim (Archives of Virology, 1984)

Synergistic effects of Aroclor 1254 and mirex on the semen characteristics of American Kestrels - D. M. Bird; P. H. Tucker; Glen A. Fox; P. C. Lagu (Archives of Environmental Contamination and Toxicology, 1983)

Ecological significance of behavioral and hormonal abnormalities in breeding ring doves fed an organochlorine chemical mixture - M. L. B. McArthur; G. A. Fox; D. B. Peakall; B. J. R. Philogne (Archives of Environmental Contamination and Toxicology, 1983)

A comparison of cervical cytomegalovirus (CMV) excretion in gynaecological patients and post-partum women - Wendy A. Knowles; Sylvia D. Gardner; H. Fox (Archives of Virology, 1982)

Populations of aphids on named varieties of Irish potatoes - B. J. Landis; D. M. Powell; Lee Fox (American Journal of Potato Research, 1972)